Optical film, polarizing plate, image display device, and method for selecting optical film

By forming an optical film with a low refractive index layer on the biaxially stretched plastic film, the problem of rainbow unevenness in the prior art is solved, and the effect of suppressing rainbow unevenness without increasing the in-plane phase difference is achieved.

CN119439353APending Publication Date: 2025-02-14DAI NIPPON PRINTING CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411780310.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-09-30
Filing Date
2020-09-30
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, when using a biaxially stretched plastic film as the polarizer protective film, it is difficult to suppress rainbow unevenness during naked eyes without increasing the in-plane phase difference.

Method used

An optical film with a low refractive index layer on the plastic film is used. Specifically, a biaxially stretched plastic film with an in-plane phase difference of less than 2500 nm is used, and a low refractive index layer is formed on its most surface to ensure the ΔEab of the optical film. The difference between the maximum and minimum values ​​is less than 17.0.

Benefits of technology

It effectively suppresses rainbow unevenness during naked eye observation, and does not need to improve the in-plane phase difference, and improves the performance of the optical film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119439353A_ABST
    Figure CN119439353A_ABST
Patent Text Reader

Abstract

The invention provides an optical film, a polarizing plate, an image display device, and a method for selecting the optical film. An optical film having a low refractive index layer on a plastic film, the plastic film being a biaxially stretched plastic film having an in-plane phase difference of 2500 nm or less, the optical film having the low refractive index layer positioned on the outermost surface, the optical film having a region in which [Delta] Eab satisfies a specific condition, [Delta] Eab is calculated from the difference between an L * value, a * value, and b * value obtained by measuring a laminate (1) including the optical film, the polarizer, and the surface light source under specific conditions, and an L * value, a * value, and b * value obtained by measuring a laminate (2) including the polarizer and the surface light source under specific conditions.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application. The application number of the original application is 202080077474.X, the application date is September 30, 2020, and the name of the invention is "Optical film, polarizing plate, image display device and method for selecting optical film". Technical Field

[0002] The present disclosure relates to an optical film, a polarizing plate, an image display device, and a method for selecting an optical film. Background Art

[0003] Various optical plastic films are often used in optical components such as image display devices. For example, in an image display device having a polarizing plate on a display element, a plastic film is used to protect a polarizer constituting the polarizing plate.

[0004] The plastic film for image display devices used as a polarizer protective film or the like preferably has excellent mechanical strength. Therefore, as the plastic film for image display devices, a stretched plastic film is preferably used.

[0005] When a stretched plastic film is placed on a polarizer, the stretched plastic film disturbs the polarization state of the linear polarized light passing through the polarizer, so there is a problem that rainbow pattern unevenness is observed. In order to solve this problem, the techniques of patent documents 1 to 3 are proposed. Hereinafter, in this specification, "rainbow pattern unevenness" is sometimes referred to as "rainbow unevenness".

[0006] Patent document 1 discloses a liquid crystal display device that can eliminate rainbow unevenness when viewing images through polarized sunglasses by setting the light source of the image display device to a specific white light source, increasing the in-plane phase difference (delay) of the stretched plastic film to above 3000nm and below 30000nm, and configuring the absorption axis of the polarizer and the slow axis of the stretched plastic film at approximately 45 degrees.

[0007] However, the method of Patent Document 1 requires the use of a stretched plastic film having a large in-plane phase difference. Furthermore, a stretched plastic film having a large in-plane phase difference is generally uniaxially stretched, and thus has the problem of being easily cracked in the stretching direction.

[0008] Patent Document 2 discloses a polarizer protection film having a reflectance within a specific range at a Brewster angle. Patent Document 3 discloses a polarizer protection film having a difference of 20% or less between the reflectance of a P wave and the reflectance of an S wave at an incident angle of 50 degrees.

[0009] Regarding the polarizing plate protective films of Patent Documents 2 and 3, rainbow unevenness during visual observation is eliminated by reducing the reflectivity difference between the polarization components of light from the inside of the image display device toward the observer side, namely, the P wave and the S wave, without increasing the in-plane phase difference of the film as in Patent Document 1.

[0010] Biaxially stretched plastic films are generally obtained by obtaining a cast film formed by melt-extruding the plastic constituting the film, and then stretching the cast film in the conveying direction and the width direction. At this time, it is known that the orientation angle varies depending on the position in the width direction due to the so-called bow phenomenon.

[0011] It is generally believed that the optical properties of a biaxially stretched plastic film are stable near the center in the width direction. However, the polarizing plate protective films of Patent Documents 2 and 3 may not eliminate rainbow unevenness even if biaxially stretched plastic films taken from near the center are used.

[0012] Prior art literature

[0013] Patent Literature

[0014] Patent Document 1: Japanese Patent Application Publication No. 2011-107198

[0015] Patent Document 2: Japanese Patent Application Publication No. 2009-14886

[0016] Patent Document 3: Japanese Patent Application Publication No. 2010-204630 Summary of the invention

[0017] Problems to be solved by the invention

[0018] The present disclosure provides an optical film capable of suppressing rainbow unevenness when observed with the naked eye without increasing the in-plane phase difference, and a polarizing plate and an image display device using the optical film. In addition, the present disclosure provides a method for selecting an optical film capable of suppressing rainbow unevenness when observed with the naked eye without increasing the in-plane phase difference.

[0019] Means for solving problems

[0020] The present disclosure provides the following [1] to [4].

[0021] [1] An optical film having a low refractive index layer on a plastic film, wherein:

[0022] The plastic film is a biaxially stretched plastic film with an in-plane phase difference of less than 2500 nm.

[0023] The low refractive index layer is located on the outermost surface of the optical film.

[0024] The optical film has a region where the difference between the maximum value and the minimum value of ΔEab is less than 17.0,

[0025] Here, measurement 1 is performed on laminate 1 to calculate the L* value, a* value, and b* value of the L*a*b* colorimetric system, and measurement 2 is performed on laminate 2 to calculate the L* value, a* value, and b* value of the L*a*b* colorimetric system. Based on the results of measurement 1 and measurement 2, ΔEab is calculated according to condition 1.

[0026] <Measurement 1>

[0027] A laminate 1 is prepared by laminating a polarizer and the optical film in this order on a surface light source, wherein in the laminate 1, the optical film is arranged in such a manner that the surface of the low refractive index layer side faces the side opposite to the polarizer, and further, the polarizer is arranged in such a manner that the angle formed by the absorption axis of the polarizer and the left-right direction or the up-down direction of the surface light source is within ±5 degrees, and the angle formed by the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film is within 90 degrees ±5 degrees,

[0028] The surface light source of the stacked body 1 is made to display white, and the transmitted light emitted from the low refractive index layer side of the stacked body 1 is measured 1 degree at a range of an elevation angle of 0 degrees to 80 degrees and an azimuth angle of 0 degrees to 359 degrees. The L* value, a* value and b* value of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area of ​​the transmitted light is any 1mm in the plane. 2 Above and 10mm 2 The following areas;

[0029] <Measurement 2>

[0030] A laminate 2 is prepared by laminating a polarizer on the same surface light source as that in the measurement 1, and the absorption axis of the polarizer is arranged in the same direction as that in the measurement 1 relative to the surface light source.

[0031] The surface light source of the stacked body 2 is made to display white, and the transmitted light emitted from the polarizer side of the stacked body 2 is measured 1 degree at a range of an elevation angle of not less than 0 degree and not more than 80 degrees and an azimuth angle of not less than 0 degree and not more than 359 degrees, and the L* value, a* value and b* value of the L*a*b* colorimetric system are calculated based on the transmitted light at each angle, and the measurement area of ​​the transmitted light is substantially consistent with that of measurement 1 within the plane;

[0032] <Condition 1>

[0033] At all elevation angles and all azimuth angles, ΔL* is calculated by subtracting the L* value of measurement 2 from the L* value of measurement 1, and all values ​​of ΔL* from the maximum value to the minimum value are grayscaled with a specified color tone and displayed in grayscale in a two-dimensional coordinate system in which concentric circles represent elevation angles and vertical and horizontal circles represent azimuth angles.

[0034] It was confirmed that there were two regions where ΔL* was distributed in concentric circles in the two-dimensional coordinates, and that the two regions were located at approximately symmetrical positions in the two-dimensional coordinates.

[0035] Regarding the elevation angle at the center of the region where ΔL* is distributed in concentric circles, let one elevation angle be α degrees and the other elevation angle be β degrees.

[0036] ΔEab at each azimuth angle is calculated based on the difference between the L* value, a* value, and b* value of measurement 1 when the azimuth angle is greater than 0 degrees and less than 359 degrees when the elevation angle is (α+β) / 2, and the L* value, a* value, and b* value of measurement 2 when the azimuth angle is greater than 0 degrees and less than 359 degrees when the elevation angle is (α+β) / 2.

[0037] [2] A polarizing plate comprising: a polarizer; a first transparent protective plate disposed on one side of the polarizer; and a second transparent protective plate disposed on the other side of the polarizer, wherein at least one of the first transparent protective plate and the second transparent protective plate is the optical film described in [1].

[0038] [3] An image display device comprising a display element and a polarizer and an optical film arranged on the light emitting surface side of the display element, wherein the optical film is the optical film described in [1] and is arranged in such a manner that the angle formed by the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film is within 90 degrees ± 5 degrees, and is arranged in such a manner that the surface of the low refractive index layer side of the optical film faces the side opposite to the display element.

[0039] [4] An image display device having a polarizer and an optical film on a light emitting surface of a display element, wherein:

[0040] The image display device is configured in such a way that the angle formed by the absorption axis direction of the polarizer and the left-right direction or the up-down direction of the display element is within ±5 degrees.

[0041] The optical film is configured in such a way that the angle formed by the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film is within 90 degrees ± 5 degrees,

[0042] The optical film is formed by having a low refractive index layer on a biaxially stretched plastic film having an in-plane phase difference of less than 2500 nm, wherein the low refractive index layer is located on the outermost surface of the optical film and has a region where the difference between the maximum and minimum values ​​of ΔEab is less than 17.0,

[0043] Here, measurement 1A is performed on laminate 1A to calculate the L* value, a* value, and b* value of the L*a*b* colorimetric system. Measurement 2A is performed on laminate 2A to calculate the L* value, a* value, and b* value of the L*a*b* colorimetric system. Based on the results of measurement 1A and measurement 2A, ΔEab is calculated according to condition 1A.

[0044] <Measurement 1A>

[0045] A laminate 1A is prepared by laminating a polarizer and the optical film in this order on a display element, wherein in the laminate 1A, the optical film is arranged in such a manner that the surface on the low refractive index layer side faces the side opposite to the polarizer, and further, the polarizer is arranged in such a manner that the angle formed by the absorption axis of the polarizer and the left-right direction or the up-down direction of the display element is within ±5 degrees, and the angle formed by the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film is within 90 degrees ±5 degrees,

[0046] The display element of the stacked body 1A is made to display white, and the transmitted light emitted from the low refractive index layer side of the stacked body 1A is measured 1 degree at a range of an elevation angle of 0 degree to 80 degrees and an azimuth angle of 0 degree to 359 degrees, and the L* value, a* value and b* value of the L*a*b* colorimetric system are calculated from the transmitted light at each angle, and the measurement area of ​​the transmitted light is an arbitrary 1mm in the plane. 2 Above and 10mm 2 The following areas;

[0047] <Measurement 2A>

[0048] A laminate 2A is prepared by laminating a polarizing element on the same display element as that of the measurement 1A.

[0049] The display element of the stacked body 2A is made to display white, and the transmitted light emitted from the polarizer side of the stacked body 2A is measured 1 degree at a range of an elevation angle of not less than 0 degree and not more than 80 degrees and an azimuth angle of not less than 0 degree and not more than 359 degrees, and the L* value, a* value and b* value of the L*a*b* colorimetric system are calculated based on the transmitted light at each angle, and the measurement area of ​​the transmitted light is substantially consistent with that of the measurement 1A in the plane;

[0050] <Condition 1A>

[0051] At all elevation angles and all azimuth angles, ΔL* is calculated by subtracting the L* value of measurement 2A from the L* value of measurement 1A, and all values ​​of ΔL* from the maximum value to the minimum value are grayscaled with a specified color tone and displayed in grayscale in a two-dimensional coordinate system in which concentric circles represent elevation angles and vertical and horizontal circles represent azimuth angles.

[0052] It was confirmed that there were two regions where ΔL* was distributed in concentric circles in the two-dimensional coordinates, and that the two regions were located at approximately symmetrical positions in the two-dimensional coordinates.

[0053] Regarding the elevation angle at the center of the region where ΔL* is distributed in concentric circles, let one elevation angle be α degrees and the other elevation angle be β degrees.

[0054] ΔEab at each azimuth angle is calculated based on the difference between the L* value, a* value, and b* value of measurement 1A when the azimuth angle is greater than 0 degrees and less than 359 degrees when the elevation angle is (α+β) / 2 and the L* value, a* value, and b* value of measurement 2A when the azimuth angle is greater than 0 degrees and less than 359 degrees when the elevation angle is (α+β) / 2.

[0055] [5] A method for selecting an optical film for an image display device, wherein the image display device comprises a polarizer and an optical film on a light emitting surface of a display element, and the polarizer is arranged in such a way that the absorption axis direction is parallel to the left-right direction or the up-down direction of the display element, wherein:

[0056] The optical film X is formed by having a low refractive index layer on a biaxially stretched plastic film having an in-plane phase difference of less than 2500 nm, the low refractive index layer is located on the outermost surface of the optical film X, and has a region where the difference between the maximum value and the minimum value of ΔEab is less than 17.0 as a judgment condition, and the optical film X that satisfies the judgment condition is selected as the optical film,

[0057] Here, measurement 1B is performed on laminate 1B to calculate the L* value, a* value, and b* value of the L*a*b* colorimetric system. Measurement 2B is performed on laminate 2B to calculate the L* value, a* value, and b* value of the L*a*b* colorimetric system. Based on the results of measurement 1B and measurement 2B, ΔEab is calculated according to condition 1B.

[0058] <Measurement 1B>

[0059] A laminate 1B is prepared in which a polarizer and the optical film X are laminated in this order on a display element, wherein in the laminate 1B, the optical film is arranged in such a manner that the surface of the low refractive index layer side faces the side opposite to the polarizer, and further, the polarizer is arranged in such a manner that the angle formed by the absorption axis of the polarizer and the left-right direction or the up-down direction of the display element is within ±5 degrees, and the angle formed by the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film X is within 90 degrees ±5 degrees,

[0060] The display element of the stacked body 1B was made to display white, and the transmitted light emitted from the low refractive index layer side of the stacked body 1B was measured 1 degree at a range of an elevation angle of 0 degree to 80 degrees and an azimuth angle of 0 degree to 359 degrees, and the L* value, a* value and b* value of the L*a*b* color system were calculated from the transmitted light at each angle. The measurement area of ​​the transmitted light was an arbitrary 1 mm2 area within the surface. 2 Above and 10mm 2 The following areas;

[0061] <Measurement 2B>

[0062] A laminate 2B is prepared in which a polarizer is laminated on the same display element as that of the measurement 1B.

[0063] The display element of the stacked body 2B is made to display white, and the transmitted light emitted from the polarizer side of the stacked body 2B is measured 1 degree at a range of an elevation angle of not less than 0 degree and not more than 80 degrees and an azimuth angle of not less than 0 degree and not more than 359 degrees, and the L* value, a* value and b* value of the L*a*b* colorimetric system are calculated based on the transmitted light at each angle, and the measurement area of ​​the transmitted light is substantially consistent with that of the measurement 1B in the plane;

[0064] <Condition 1B>

[0065] At all elevation angles and all azimuth angles, ΔL* is calculated by subtracting the L* value of measurement 2B from the L* value of measurement 1B, and all values ​​of ΔL* from the maximum value to the minimum value are grayscaled with a specified color tone and displayed in grayscale in a two-dimensional coordinate system in which concentric circles represent elevation angles and vertical and horizontal circles represent azimuth angles.

[0066] It was confirmed that there were two regions where ΔL* was distributed in concentric circles in the two-dimensional coordinates, and that the two regions were located at approximately symmetrical positions in the two-dimensional coordinates.

[0067] Regarding the elevation angle at the center of the region where ΔL* is distributed in concentric circles, let one elevation angle be α degrees and the other elevation angle be β degrees.

[0068] Based on the difference between the L* value, a* value, and b* value of measurement 1B with an azimuth angle of greater than 0 degrees and less than 359 degrees when the elevation angle is (α+β) / 2, and the L* value, a* value, and b* value of measurement 2B with an azimuth angle of greater than 0 degrees and less than 359 degrees when the elevation angle is (α+β) / 2, ΔEab at each azimuth angle is calculated. At this time, the difference between the maximum and minimum values ​​of ΔEab is less than 17.0.

[0069] Effects of the Invention

[0070] The optical film disclosed herein, and the polarizing plate and image display device using the optical film can suppress rainbow unevenness when observed with the naked eye without increasing the in-plane phase difference to more than 3000 nm. In addition, the selection method of the optical film disclosed herein can efficiently select an optical film that can suppress rainbow unevenness when observed with the naked eye without increasing the in-plane phase difference. BRIEF DESCRIPTION OF THE DRAWINGS

[0071] Figure 1 is a cross-sectional view showing one embodiment of the optical film of the present disclosure.

[0072] Figure 2 This is a cross-sectional view for explaining the arrangement of the laminated body 1 used in the measurement 1 in the thickness direction.

[0073] Figure 3 It is a cross-sectional view for explaining the arrangement of the laminated body 2 used in the measurement 2 in the thickness direction.

[0074] Figure 4 The value (ΔL*) obtained by subtracting the L* value of measurement 2 from the L* value of measurement 1 is grayed out with a predetermined tone and displayed in grayscale on a two-dimensional coordinate system in which concentric circles represent elevation angles and vertical and horizontal lines represent azimuth angles.

[0075] Figure 5 is a cross-sectional view showing one embodiment of the polarizing plate of the present disclosure.

[0076] Figure 6 is a cross-sectional view showing one embodiment of the image display device of the present disclosure.

[0077] Figure 7 This is a plan view of five measurement positions in a sample for explaining how to calculate the in-plane phase difference and the like from the sample.

[0078] Figure 8 This is a cross-sectional photograph of an example of a low refractive index layer in which hollow particles and non-hollow particles are uniformly dispersed.

[0079] Fig. 9 This is a cross-sectional photograph of an example of a low refractive index layer in which hollow particles and non-hollow particles are not uniformly dispersed.

[0080] Fig.10 It is a figure which shows schematically the state of a continuous folding test.

[0081] Fig.11 is used to explain condition A [+α B -(-α B )]、[+α G -(-α G )] and [+α R -(-α R )].

[0082] Description of symbols

[0083] 10: Plastic film;

[0084] 20: Hard coating;

[0085] 30: low refractive index layer;

[0086] 100: optical film;

[0087] 200: surface light source;

[0088] 300: Polarizer;

[0089] 400: adhesive layer;

[0090] 500: 1st transparent protective plate;

[0091] 600: second transparent protective plate;

[0092] 700: Polarizing plate;

[0093] 800: display element;

[0094] 1000: image display device;

[0095] X: laminate 1;

[0096] Y: Laminated body 2. DETAILED DESCRIPTION

[0097] Hereinafter, embodiments of the present disclosure will be described.

[0098] [Optical film]

[0099] The optical film disclosed herein comprises a low refractive index layer on a plastic film, wherein the plastic film is a biaxially stretched plastic film having an in-plane phase difference of less than 2500 nm, wherein the low refractive index layer is located on the outermost surface of the optical film, and the optical film has an area where the difference between the maximum and minimum values ​​of ΔEab is less than 17.0.

[0100] Here, measurement 1 is performed on laminate 1 to calculate the L* value, a* value, and b* value of the L*a*b* colorimetric system. Measurement 2 is performed on laminate 2 to calculate the L* value, a* value, and b* value of the L*a*b* colorimetric system. Based on the results of measurement 1 and measurement 2, ΔEab is calculated according to condition 1.

[0101] <Measurement 1>

[0102] A laminate 1 is prepared by laminating a polarizer and the optical film in this order on a surface light source, wherein in the laminate 1, the optical film is arranged with the surface of the low refractive index layer facing the side opposite to the polarizer, and further, the polarizer is arranged with the angle formed by the absorption axis of the polarizer and the left-right direction or the up-down direction of the surface light source within ±5 degrees, and the angle formed by the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film within 90 degrees ±5 degrees.

[0103] The surface light source of the stacked body 1 is made to display white, and the transmitted light emitted from the low refractive index layer side of the stacked body 1 is measured 1 degree at a range of an elevation angle of 0 degrees to 80 degrees and an azimuth angle of 0 degrees to 359 degrees. The L* value, a* value and b* value of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area of ​​the transmitted light is any 1mm in the plane. 2 Above and 10mm 2 The following area.

[0104] <Measurement 2>

[0105] A laminate 2 was prepared in which a polarizer was laminated on the same surface light source as in the measurement 1.

[0106] The surface light source of the stacked body 2 is made to display white, and the transmitted light emitted from the polarizer side of the stacked body 2 is measured 1 degree at a range of an elevation angle of not less than 0 degree and not more than 80 degrees and an azimuth angle of not less than 0 degree and not more than 359 degrees. The L* value, a* value and b* value of the L*a*b* colorimetric system are calculated based on the transmitted light at each angle, and the measurement area of ​​the transmitted light is roughly consistent with measurement 1 within the plane.

[0107] Based on the measurement results, the L* value, a* value, and b* value at an azimuth angle of not less than 0 degrees and not more than 359 degrees when the elevation angle is (α+β) / 2 are respectively confirmed.

[0108] <Condition 1>

[0109] At all elevation angles and all azimuth angles, ΔL* is calculated by subtracting the L* value of measurement 2 from the L* value of measurement 1, and all values ​​of ΔL* from the maximum value to the minimum value are grayscaled with a specified color tone and displayed in grayscale in a two-dimensional coordinate system in which concentric circles represent elevation angles and vertical and horizontal circles represent azimuth angles.

[0110] It was confirmed that there were two regions where ΔL* was distributed in concentric circles in the two-dimensional coordinates, and that the two regions were located at approximately symmetrical positions in the two-dimensional coordinates.

[0111] Regarding the elevation angle at the center of the region where ΔL* is distributed in concentric circles, let one elevation angle be α degrees and the other elevation angle be β degrees.

[0112] ΔEab at each azimuth angle is calculated based on the difference between the L* value, a* value, and b* value of measurement 1 when the azimuth angle is greater than 0 degrees and less than 359 degrees when the elevation angle is (α+β) / 2, and the L* value, a* value, and b* value of measurement 2 when the azimuth angle is greater than 0 degrees and less than 359 degrees when the elevation angle is (α+β) / 2.

[0113] In this specification, measurement 1 and measurement 2, as well as the measurements described later (in-plane phase difference, phase difference in the thickness direction, direction of the slow axis, surface roughness of the low refractive index layer, etc.), are performed in an atmosphere with a temperature of 23°C ± 5°C and a relative humidity of 40% RH or more and 65% RH or less, unless otherwise specified. In addition, before each measurement, the measurement sample is exposed to the atmosphere for more than 30 minutes.

[0114] Figure 1 1 is a cross-sectional view showing an embodiment of the optical film 100 of the present disclosure. Figure 1 As shown, the optical film 100 of the present disclosure has a low refractive index layer 30 on a plastic film 10 .

[0115] The optical film 100 of the present disclosure may have layers other than the plastic film 10 and the low refractive index layer 30. Examples of the layers other than the plastic film 10 and the low refractive index layer 30 include a hard coat layer, an antiglare layer, and a high refractive index layer. Figure 1 The optical film 100 has a hard coating layer 20 between a plastic film 10 and a low refractive index layer 30 .

[0116] About Measurement 1

[0117] Measurement 1 can be performed as follows (1-1)-(1-2).

[0118] (1-1) A laminate 1 is prepared by laminating a polarizer and an optical film in this order on a surface light source, wherein in the laminate 1, the optical film is arranged with the surface of the low refractive index layer facing the side opposite to the polarizer, and further, the polarizer is arranged with the angle formed by the absorption axis of the polarizer and the left-right direction or the up-down direction of the surface light source within ±5 degrees, and the angle formed by the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film within 90 degrees ±5 degrees.

[0119] Figure 2 This is a cross-sectional view for explaining the arrangement of the laminated body 1 in the thickness direction used in the above (1-1).

[0120] exist Figure 2 In the laminate 1 (X), the surface light source 200, the polarizer 300 and the optical film 100 are laminated together via the adhesive layer 400. Figure 2 As shown, the surface light source, polarizer and optical film are preferably bonded together by an adhesive layer or the like. Furthermore, the bonding mentioned above can be performed in appearance only, for example, it can be a temporary bonding performed by liquids such as water and solvents. In addition, the laminate 1 can also have an optically isotropic film. For example, an optically isotropic film can be provided on one or both sides of the polarizer as a polarizer protective film.

[0121] Regarding the adhesive layer used in the production of the laminate 1 and the laminate 2 described later, the refractive index is preferably greater than 1.42 and less than 1.53, and the thickness is preferably greater than 15 μm and less than 40 μm. Regarding the adhesive layer, the refractive index is more preferably greater than 1.45 and less than 1.50, and the thickness is more preferably greater than 20 μm and less than 30 μm. If the refractive index and thickness of the adhesive layer are within the range, it can be said that there is no substantial effect on ΔEab described later. In this specification, the refractive index is a dimensionless parameter. The adhesive layer used in the production of the laminate 1 and the laminate 2 described later preferably has substantially no internal haze.

[0122] Furthermore, as the adhesive layer, a commonly used adhesive layer such as a curable adhesive layer, a pressure-sensitive adhesive layer (so-called adhesive layer), and a heat-sensitive adhesive layer (heat seal layer) can be used.

[0123] In the above (1-1), the polarizer is configured in a manner that the absorption axis of the polarizer is approximately parallel to the left-right direction or the up-down direction of the surface light source. In this specification, approximately parallel means that the difference between the absorption axis of the polarizer and the left-right direction or the up-down direction of the surface light source is within ±5 degrees, preferably within ±3 degrees, and more preferably within ±1 degree.

[0124] If the planar shape of the surface light source is a rectangle or a square, it is easy to identify the left-right direction or the up-down direction. In addition, there is no need to distinguish left-right and up-down.

[0125] When the top view shape of the surface light source is a shape other than a rectangle or square (circle, triangle, etc.), a rectangle or square with the largest area that does not protrude from the outer frame shape of the surface light source is depicted, and the left-right direction or the up-down direction can be determined based on the depicted rectangle or square.

[0126] Furthermore, in the above (1-1), the configuration in which the angle between the absorption axis of the polarizer and the left-right direction or the up-down direction of the surface light source is within ±5 degrees is made in consideration of the following situation: the polarizer on the light emitting surface side of a commonly used image display device is configured in this manner.

[0127] In the above (1-1), the absorption axis of the polarizer is arranged to be approximately perpendicular to the slow axis of the biaxially stretched plastic film of the optical film. In this specification, approximately perpendicular means that the angle between the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film is within 90 degrees ± 5 degrees, preferably within 90 degrees ± 3 degrees, and more preferably within 90 degrees ± 1 degree.

[0128] The slow axis refers to the direction of the maximum refractive index in the plane of the biaxially stretched plastic film. If the direction of the slow axis in the plane of the biaxially stretched plastic film is uneven, the direction of the slow axis in the plane of the biaxially stretched plastic film refers to the average direction of the slow axis in the plane of the biaxially stretched plastic film.

[0129] In the above (1-1), the polarizer is preferably a polarizer with a polarization degree of 99.00% or more and an average transmittance of 35% or more, more preferably a polarization degree of 99.90% or more and an average transmittance of 37% or more, and further preferably a polarization degree of 99.95% or more and an average transmittance of 40% or more. In addition, in this specification, the average transmittance refers to the average of the spectral transmittance with a wavelength of 400nm or more and 700nm or less. The measurement wavelength interval of the average transmittance is 5nm.

[0130] In addition, the polarizer may have an optically isotropic film on one or both sides thereof. In addition, the polarizer and the optically isotropic film may be bonded together via an adhesive layer.

[0131] The polarizer used in Measurement 1 and Measurement 2 may be a polarizer pre-arranged on the display element or a polarizer prepared separately.

[0132] In the above (1-1), the surface light source is not particularly limited as long as it can display white.

[0133] The light emitted from the surface light source passes through the polarizer and becomes linearly polarized light, which enters the optical film. The linearly polarized light entering the optical film can be simulated as light emitted from a display element of a common image display device and is light (linearly polarized light) that has passed through the observation side polarizer.

[0134] The surface light source may be, for example, a commonly used image display device such as a liquid crystal display device or an organic EL display device. However, in the case where the image display device has an observation side polarizer on the display element, the portion other than the observation side polarizer is regarded as the surface light source. This is because the observation side polarizer may be a polarizer of the laminate 1 and the laminate 2. In addition, in the case where the surface light source is a liquid crystal display device, as the backlight source of the liquid crystal display device, a backlight source using quantum dots and a backlight source using white light emitting diodes may be cited.

[0135] Furthermore, a laminated body in which an optical film is disposed on an image display device having an observation-side polarizer on a display element can be regarded as laminated body 1 used in measurement 1 as long as the other conditions of measurement 1 are satisfied.

[0136] In addition, an image display device having an observation-side polarizer on a display element can be regarded as the laminated body 2 used in Measurement 2 as long as the other conditions of Measurement 2 are satisfied.

[0137] (1-2) The surface light source of the laminate 1 is made to display white, and the transmitted light emitted from the low refractive index layer side of the laminate 1 is measured 1 degree at a range of an elevation angle of 0 degrees to 80 degrees and an azimuth angle of 0 degrees to 359 degrees, and the L* value, a* value and b* value of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area of ​​the transmitted light is any 1mm within the surface. 2 Above and 10mm 2 The following area.

[0138] In the above (1-2), the measurement area is set to 1 mm 2 The above is based on the consideration that if the area is too small, it will be difficult for people to recognize it with their eyes. In addition, the measurement area is set to 10mm 2 The following is made in consideration of suppressing the influence of the emission angle distribution of the surface light source and considering that if the area is too large, ΔEab will be averaged, making it difficult to correlate with the visual result.

[0139] The reason why the maximum value of the elevation angle is set to 80 degrees is that, generally, outgoing light at an elevation angle exceeding 80 degrees is close to parallel to a plane, and therefore it is difficult to detect the outgoing light.

[0140] In the above (1-2), the measurement area is preferably 1 mm2 Above and 5mm 2 the following.

[0141] In the above (1-2), the interval between the stack 1 and the measuring device for transmitted light is preferably set to be greater than 0 mm and less than 1.5 mm, more preferably to be greater than 0.5 mm and less than 1.5 mm, and further preferably to be 1.0 mm. By setting it to the above interval, the deformation of the stack 1 caused by the weight of the measuring device can be suppressed, and the expansion of the emitted light can be suppressed, which makes it easy to reduce the measurement error. Similarly, in the later-described (2-2), the interval between the stack 2 and the measuring device for transmitted light is also preferably set to the above range.

[0142] The measurement and analysis in (1-2) described above, (2-2) described later, and (3-1) to (3-4) described later can be performed by, for example, an instrument with the trade name "EzContrast" of ELDIM.

[0143] In this specification, the L* value, the a* value, and the b* value are based on the L*a*b* colorimetric system standardized by the International Commission on Illumination (CIE) in 1976. The L*a*b* colorimetric system is adopted in JIS Z8781-4:2013.

[0144] About Measurement 2

[0145] Measurement 2 can be performed as follows (2-1) to (2-2).

[0146] (2-1) A laminate 2 is prepared in which a polarizer is laminated on the same surface light source as in the measurement 1. The absorption axis of the polarizer is arranged in the same direction with respect to the surface light source as in the measurement 1. The polarizer used in the measurement 2 is the same as that used in the measurement 1.

[0147] Figure 3 This is a cross-sectional view for explaining the arrangement of the laminated body 2 in the thickness direction used in the above (2-1).

[0148] exist Figure 3 In the laminated body 2 (Y), the surface light source 200 and the polarizer 300 are laminated with the adhesive layer 400 interposed therebetween. Figure 3 As shown, the surface light source and the polarizer are preferably bonded together by an adhesive layer, etc. Furthermore, the bonding mentioned above only needs to be performed in appearance, for example, temporary bonding by liquids such as water and solvents may also be performed.

[0149] In the above (2-1), the absorption axis of the polarizer is arranged in the same direction relative to the surface light source as in the measurement 1. For example, in the measurement 1, when the absorption axis of the polarizer is arranged in parallel with the left-right direction of the surface light source, the same arrangement is also used in the above (2-1).

[0150] (2-2) The surface light source of the laminate 2 is made to display white, and the transmitted light emitted from the polarizer side of the laminate 2 is measured 1 degree at a range of an elevation angle of 0 degrees to 80 degrees and an azimuth angle of 0 degrees to 359 degrees, and the L* value, a* value and b* value of the L*a*b* colorimetric system are calculated based on the transmitted light at each angle. The measurement area of ​​the transmitted light is substantially consistent with that of measurement 1 within the plane.

[0151] In the above (2-2), making the measurement area of ​​the transmitted light roughly consistent with measurement 1 in the plane means that: when stack 1 and stack 2 are overlapped and viewed from above, the distance between the center of the measurement area of ​​the transmitted light in measurement 1 and the center of the measurement area of ​​the transmitted light in measurement 2 is within 0.5 mm, preferably within 0.3 mm, and more preferably within 0.1 mm.

[0152] As described in (1-1) above, the surface light source used in measurement 1 and measurement 2 is not particularly limited as long as it can display white, but in order to perform stable measurement, it is preferred that the average of the L* value, a* value, and b* value be displayed as follows (a1) to (a3) ​​in the state of the laminate 2. In other words, in order to perform stable measurement, the average of the L* value, a* value, and b* value of measurement 2 is preferably displayed in the following range.

[0153] (a1) The average of the L* values ​​at all angles obtained in the measurement of (2-2) above is 95 or more and 105 or less. The average of the L* values ​​at all angles is more preferably 95 or more and 100 or less.

[0154] (a2) The average of the a* values ​​of all angles obtained in the measurement of (2-2) above is -10 or more and 10 or less. The average of the a* values ​​of all angles is more preferably -5 or more and 5 or less.

[0155] (a3) The average of the b* values ​​at all angles obtained in the measurement of (2-2) above is -10 or more and 10 or less. The average of the b* values ​​at all angles is more preferably -5 or more and 5 or less.

[0156] In addition, in order to perform more stable measurement, it is more preferred that the deviation (3σ) of the L* value, a* value, and b* value in the state of the laminate 2 is displayed as the surface light source of (b1) to (b3) below. In other words, in order to perform stable measurement, the deviation (3σ) of the L* value, a* value, and b* value of the measurement 2 is preferably displayed in the following range.

[0157] (b1) The deviation (3σ) of the L* value at all angles obtained in the measurement of (2-2) above is 120 or less. The deviation (3σ) of the L* value at all angles is more preferably 115 or less.

[0158] (b2) The deviation (3σ) of the absolute value of the a* value of all angles obtained in the measurement of (2-2) above is 15 or less.

[0159] (b3) The deviation (3σ) of the absolute value of the b* value at all angles obtained in the measurement of (2-2) above is 15 or less.

[0160] In order to more easily suppress rainbow unevenness, the surface light source preferably satisfies the following condition A. Satisfying condition A means that at least one of the half-maximum widths of the peaks of intensity in the blue wavelength region, the green wavelength region, and the red wavelength region is greater than a predetermined value (greater than 10 nm).

[0161] Fig.11 is used to explain condition A [+α B -(-α B )]、[+α G -(-α G )] and [+α R -(-α R )]. In addition, Fig.11 The spectral spectrum is the spectral spectrum of the surface light source of the commonly used organic EL element.

[0162] <Condition A>

[0163] The first polarizer is arranged on the surface light source, and the intensity of the light L1 emitted from the first polarizer in the vertical direction is measured for each 1nm wavelength. The wavelength region of blue is set to be greater than 400nm and less than 500nm, the wavelength region of green is set to be greater than 500nm and less than 570nm, and the wavelength region of red is set to be greater than 570nm and less than 780nm. The maximum intensity of the blue wavelength region of L1 is set to B max , the maximum intensity of the green wavelength region of L1 is set to G max , the maximum intensity of the red wavelength region of L1 is set to R max .

[0164] will represent the Bmax The wavelength is set to L1λ B , will represent the G max The wavelength is set to L1λ G , will represent the R max The wavelength is set to L1λ R .

[0165] will represent the B max The wavelength of the intensity is less than 1 / 2 and is located at L1λ B The minimum wavelength on the negative side is set to -α B , will represent the B max The wavelength of the intensity is less than 1 / 2 and is located at L1λ B The minimum wavelength on the positive side is set to +α B , will represent the G max The wavelength of the intensity is less than 1 / 2 and is located at L1λ G The maximum wavelength on the negative side is set to -α G , will represent the G max The wavelength of the intensity is less than 1 / 2 and is located at L1λ G The minimum wavelength on the positive side is set to +α G , will represent the R max The wavelength of the intensity is less than 1 / 2 and is located at L1λ R The maximum wavelength on the negative side is set to -α R , will represent the R max The wavelength of the intensity is less than 1 / 2 and is located at L1λ R The maximum wavelength on the positive side is set to +α R .

[0166] [+α B -(-α B )]、[+α G -(-α G )] and [+α R -(-α R )] at least any one of which is greater than 10 nm.

[0167] Regarding condition A, it is more preferred that [+α B -(-α B )]、[+α G -(-α G )] and [+α R -(-α R )] are shown to be greater than 10 nm, and more preferably, all three are shown to be greater than 10 nm.

[0168] 《About Condition 1》

[0169] In Condition 1, the difference between the maximum and minimum values ​​of ΔEab calculated in the following steps is calculated based on the L* value, a* value, and b* value obtained in Measurement 1 and Measurement 2. The optical film of the present disclosure needs to have a region where the difference is less than 17.0.

[0170] <Condition 1>

[0171] At all elevation angles and all azimuth angles, ΔL* is calculated by subtracting the L* value of measurement 2 from the L* value of measurement 1, and all values ​​of ΔL* from the maximum value to the minimum value are grayscaled in a specified tone and displayed in grayscale in a two-dimensional coordinate system in which concentric circles represent the elevation angle and vertical and horizontal lines represent the azimuth angle.

[0172] It was confirmed that there were two regions where ΔL* was distributed in concentric circles in the two-dimensional coordinates, and that the two regions were located at substantially symmetrical positions in the two-dimensional coordinates.

[0173] Regarding the elevation angles at the center of the region where ΔL* is distributed in concentric circles, one elevation angle is α degrees and the other elevation angle is β degrees.

[0174] ΔEab at each azimuth angle is calculated based on the difference between the L* value, a* value, and b* value of measurement 1 when the azimuth angle is greater than 0 degrees and less than 359 degrees when the elevation angle is (α+β) / 2, and the L* value, a* value, and b* value of measurement 2 when the azimuth angle is greater than 0 degrees and less than 359 degrees when the elevation angle is (α+β) / 2.

[0175] ΔEab is the so-called chromatic aberration.

[0176] When the "L* value, a* value and b* value" of measurement 1 and measurement 2 at a specific azimuth are defined as "L1*, a1* and b1*" and "L2*, a2* and b2*", respectively, the color difference (ΔEab) at the specific azimuth can be expressed by the following formula.

[0177] <Formula expressing color difference (ΔEab)>

[0178] ΔEab={(L1*-L2*) 2 +(a1*-a2*) 2 +(b1*-b2*) 2} 1 / 2

[0179] ΔEab of condition 1 can be calculated according to the following steps (3-1) to (3-4) based on the L* value, a* value, and b* value obtained in measurement 1 and measurement 2. That is, ΔEab of condition 1 specifies the color difference between the state with the optical film and the state without the optical film. This is to eliminate the influence of the surface light source and give correlation with rainbow unevenness.

[0180] The "(L1* 2 +a1* 2 +b1* 2 ) 1 / 2 " has no correlation with the visual recognition of rainbow unevenness. The reason for this is believed to be that the L* value of the surface light source has a greater influence.

[0181] (3-1) ΔL* is calculated at all elevation angles and all azimuth angles by subtracting the L* value of measurement 2 from the L* value of measurement 1. All values ​​of ΔL* from the maximum value to the minimum value are grayscaled with a predetermined color tone and displayed in grayscale in a two-dimensional coordinate system in which concentric circles represent elevation angles and vertical and horizontal circles represent azimuth angles.

[0182] Figure 4 This is a graph in which all values ​​of ΔL* from the maximum to the minimum are grayed out with a predetermined tone and displayed in grayscale in a two-dimensional coordinate system in which concentric circles represent elevation angles and vertical and horizontal lines represent azimuth angles. Figure 4 is the 2D coordinate of (3-1) above. In addition, Figure 4 The closer to white, the larger ΔL* is.

[0183] In addition, Figure 4 In the 2D coordinates, the center of the circular shape indicates an elevation angle of 0 degrees (in the direction perpendicular to the surface light source), and the edge indicates the maximum elevation angle. Figure 4 In the figure, the direction from the center to the right represents an azimuth of 0 degrees, the direction from the center to the top represents an azimuth of 90 degrees, the direction from the center to the left represents an azimuth of 180 degrees, and the direction from the center to the bottom represents an azimuth of 270 degrees.

[0184] The tone of the above-mentioned (3-1) is usually 2 to the power of n, and examples thereof include 16 grayscales, 32 grayscales, 64 grayscales, 128 grayscales, and 256 grayscales.

[0185] The two-dimensional coordinates of the grayscale display of (3-1) above can be produced by, for example, a device with the trade name "EzContrast" produced by ELDIM.

[0186] (3-2) It was confirmed that there were two regions where ΔL* was distributed in concentric circles in the two-dimensional coordinates, and that the two regions were located at substantially symmetrical positions in the two-dimensional coordinates.

[0187] Here, "substantially symmetrical" means that when the elevation angle and azimuth angle at the center of one area where ΔL* is distributed in concentric circles are defined as X1 and Y1, and the elevation angle and azimuth angle at the center of another area where ΔL* is distributed in concentric circles are defined as X2 and Y2, the difference between X1 and X2 is less than ±3 degrees, and the absolute value of the difference between Y1 and Y2 is less than 180 degrees ±5 degrees. The difference between X1 and X2 is preferably less than ±1 degree, and the absolute value of the difference between Y1 and Y2 is preferably less than 180 degrees ±3 degrees.

[0188] exist Figure 4 In the two-dimensional coordinates shown, there are two regions where ΔL* is distributed in concentric circles, and the two regions exist at approximately symmetrical positions in the two-dimensional coordinates.

[0189] The concentric circles at the symmetrical positions are considered to be formed for the following reason: due to the refractive index distribution in the measurement area (since the refractive index in the slow axis direction of the biaxially stretched plastic film is high, concentric circles are formed along the slow axis. Figure 4 In the case of biaxially stretched plastic film, the direction of the slow axis is Figure 4 The reflectivity of the P-wave and S-wave changes with the change in the optical distance (left-right direction) and the low-refractive index layer in the measurement area (the optical distance (the distance of the transmitted light through the low-refractive index layer) increases as it moves away from the measurement center.) In other words, the concentric circles at the symmetrical position are usually formed in the optical film having a low-refractive index layer on the biaxially stretched plastic film (measurement 1) and the single body of the biaxially stretched plastic film (in addition, the higher the in-plane phase difference, the easier it is for the concentric circles to form at the symmetrical position). Furthermore, in measurement 2, only one of the P-wave and the S-wave does not form the above-mentioned concentric circles, so in the difference (ΔL*) of the L* values ​​between measurement 1 and measurement 2, the concentric circles formed by the L* value of measurement 1 are maintained (ΔL* eliminates the influence of the light source, and accordingly, the change in the reflectivity of the P-wave and S-wave becomes more distinct, and the concentric circles are also formed more distinctly).

[0190] (3-3) Regarding the elevation angles at the center of the region where ΔL* is distributed in concentric circles, one elevation angle is α degrees and the other elevation angle is β degrees.

[0191] In the above (3-3), the "elevation angle at the center of the area where ΔL* is distributed in concentric circles" can be determined, for example, by displaying the two-dimensional coordinates on the software of the measuring device and selecting the center of the area distributed in concentric circles (for example, clicking the center of the area distributed in concentric circles with a mouse).

[0192] (3-4) Based on the measurement results, ΔEab at each azimuth angle is calculated based on the difference between the L* value, a* value, and b* value of measurement 1 when the azimuth angle is greater than 0 degrees and less than 359 degrees when the elevation angle is (α+β) / 2 and the L* value, a* value, and b* value of measurement 2 when the azimuth angle is greater than 0 degrees and less than 359 degrees when the elevation angle is (α+β) / 2. Then, the difference between the maximum and minimum values ​​of ΔEab is calculated.

[0193] In (3-4) above, if a decimal is generated in (α+β) / 2, the value is rounded up. For example, when α is 30 degrees and β is 31 degrees, ΔEab is calculated based on the L* value, a* value, and b* value when the azimuth angle is greater than 0 degrees and less than 359 degrees when the elevation angle is 31 degrees.

[0194] (α+β) / 2 is preferably 50 degrees or less, more preferably 40 degrees or less, and further preferably 30 degrees or less. By setting (α+β) / 2 to 50 degrees or less, the value of (α+β) / 2 is away from the vicinity of the Brewster angle, so that it is easy to suppress the change in the reflectivity of the P wave and the S wave at the angle before and after (α+β) / 2. The lower limit of (α+β) / 2 is not particularly limited, but is preferably 5 degrees or more, more preferably 10 degrees or more, and further preferably 15 degrees or more.

[0195] By reducing the refractive index nz in the thickness direction of the biaxially stretched plastic film, (α+β) / 2 can be easily adjusted to fall within the above range.

[0196] The optical film of the present disclosure requires that the difference between the maximum and minimum values ​​of ΔEab calculated at each azimuth (above 0 degrees and below 359 degrees) be less than 17.0. A large difference means that the hue is strongly felt at a specific azimuth. Therefore, when the difference is greater than 17.0, the hue is strongly felt at the azimuth where ΔEab represents the maximum value, and the rainbow unevenness of the naked eye cannot be suppressed.

[0197] The difference is preferably 16.0 or less, more preferably 15.0 or less, and further preferably 14.0 or less.

[0198] The lower limit of the difference is not particularly limited, but is usually about 3.0.

[0199] For example, by using a biaxially stretched plastic film satisfying Condition 2 described later, the difference can be easily made smaller than 17.0.

[0200] The reason why the measured values ​​passing through (α+β) / 2 and having an azimuth angle of 0 degree or more and 359 degrees or less are used in condition 1 is that the bright area and the dark area of ​​the concentric circles are alternately measured in the direction passing through (α+β) / 2 (refer to Figure 4), the difference between the maximum and minimum values ​​of ΔEab is theoretically the largest.

[0201] In addition, the present disclosure is characterized in that the azimuth angle passing through the center of the concentric circle ((α+β) / 2) is used instead of the Brewster's angle. The concentric circles of the above-mentioned ΔL* are affected by the in-plane phase difference (the larger the in-plane phase difference, the smaller the concentric circles). On the other hand, the Brewster's angle is dominated by the refractive index and is therefore not affected by the in-plane phase difference. Therefore, even if the "difference between the maximum and minimum values ​​of ΔEab" calculated from the measured value of the azimuth angle passing through the Brewster's angle is small, it is difficult to reduce the "difference between the maximum and minimum values ​​of ΔEab" calculated from the measured value of the azimuth angle passing through (α+β) / 2. That is, the present disclosure has a technical significance superior to that of Patent Documents 2 and 3 in that the "difference between the maximum and minimum values ​​of ΔEab" calculated from the measured value of the azimuth angle passing through (α+β) / 2 (instead of the Brewster's angle) satisfies the prescribed conditions, thereby being able to suppress the observation of rainbow unevenness.

[0202] In addition, as described later, x >n y ≥n z In a biaxially stretched plastic film having a relationship of "(α+β) / 2", the more the phase difference in the oblique direction is tilted along the direction of the slow axis, the more it gradually decreases, and becomes 0 nm near "(α+β) / 2". The inventors of the present invention have found that when the elevation angle is fixed at "(α+β) / 2", and the color tone at an azimuth angle of 0 to 359 degrees is observed, a color unevenness similar to rainbow unevenness is strongly felt. Usually, rainbow unevenness is observed in a direction in which the phase difference has a specified value. However, observation in the direction of an azimuth angle of 0 to 359 degrees when the elevation angle is fixed at "(α+β) / 2" is completely different from normal observation because the oblique phase difference in the slow axis direction is 0 nm. Therefore, in this specification, the color unevenness observed in the direction of an azimuth angle of 0 to 359 degrees when the elevation angle is fixed at "(α+β) / 2" is sometimes referred to as "color distortion" to distinguish it from "rainbow unevenness".

[0203] In the optical film, the area satisfying the condition that the difference between the maximum and minimum values ​​of ΔEab is less than 17.0 is preferably 50% or more, more preferably 70% or more, further preferably 90% or more, and further preferably 100%.

[0204] Similarly, the area satisfying various parameters other than the above-mentioned difference (in-plane phase difference, phase difference in the thickness direction, condition 2, surface roughness of the low refractive index layer, etc.) is also preferably greater than 50% in the optical film, more preferably greater than 70%, further preferably greater than 90%, and further preferably 100%.

[0205] The maximum value of ΔEab calculated at each azimuth angle (0 degree or more and 359 degrees or less) is preferably 16.0 or less, more preferably 15.0 or less, and further preferably 14.0 or less. By setting the maximum value of ΔEab to the above range, rainbow spots can be more difficult to be observed with the naked eye.

[0206] Regarding the optical film of the present disclosure, it is preferred that when the Brewster angle with respect to light of the entire visible light region incident on the optical film from the biaxially stretched plastic film side is defined as X degrees, (α+β) / 2 and X satisfy the following formula (A).

[0207] X-(α+β) / 2≤20 degrees (A)

[0208] The Brewster angle (X) can be calculated from the refractive indexes of the two substances by the following formula (B): n1 represents the refractive index on the incident side, and n2 represents the refractive index on the transmission side.

[0209] X = Arctan(n2 / n1)(B)

[0210] The optical film of the present disclosure can exert a more significant effect when the Brewster angle deviates from the center of the concentric circle ((α+β) / 2). In other words, an optical film satisfying the above formula (A) is preferred in that the effect of the present disclosure is easily exerted.

[0211] X-(α+β) / 2 is more preferably 30 degrees or more, and even more preferably 35 degrees or more. The upper limit of X-(α+β) / 2 is not particularly limited, but is about 40 degrees.

[0212] <Plastic film>

[0213] The plastic film is a biaxially stretched plastic film having an in-plane phase difference of 2500 nm or less.

[0214] By making a biaxially stretched plastic film, the mechanical strength can be improved. In addition, by making the in-plane phase difference of the biaxially stretched plastic film below 2500nm, the longitudinal and transverse stretching ratios can be set to a suitable range to make the mechanical strength better, and the tear resistance can be improved. In addition, by making the in-plane phase difference of the biaxially stretched plastic film below 2500nm, it can also contribute to the filmization of the biaxially stretched plastic film.

[0215] In order to easily suppress rainbow unevenness, the in-plane phase difference of the biaxially stretched plastic film is preferably 2000 nm or less, more preferably 1500 nm or less, more preferably 1400 nm or less, more preferably 1150 nm or less, more preferably 1000 nm or less, and more preferably 600 nm or less. When the thickness of the biaxially stretched plastic film is reduced to 10 μm or more and 50 μm or less, the in-plane phase difference is preferably 1400 nm or less.

[0216] Furthermore, when the in-plane phase difference of the biaxially stretched plastic film is too small, sometimes even biaxial stretching cannot provide sufficient mechanical strength. Therefore, the in-plane phase difference of the biaxially stretched plastic film is preferably 20 nm or more, more preferably 100 nm or more, further preferably 300 nm or more, and further preferably 520 nm or more.

[0217] The preferred range of the in-plane phase difference of the biaxially stretched plastic film is 20 nm to 2000 nm, 20 nm to 1500 nm, 20 nm to 1400 nm, 20 nm to 1150 nm, 20 nm to 1000 nm, 20 nm to 600 nm, 100 nm to 2000 nm, 100 nm to 1500 nm, 100 nm to 1400 nm, 100 nm to 1150 nm, 100 nm to 1000 nm, 100 nm to 600 nm, 100 nm to 2000 nm, 100 nm to 1500 nm, 100 nm to 1400 nm, 100 nm to 1150 nm, 100 nm to 1000 nm, 100 nm to 600 nm. 600nm or less, 300nm or more and 2000nm or less, 300nm or more and 1500nm or less, 300nm or more and 1400nm or less, 300nm or more and 1150nm or less, 300nm or more and 1000nm or less, 300nm or more and 600nm or less, 520nm or more and 2000nm or less, 520nm or more and 1500nm or less, 520nm or more and 1400nm or less, 520nm or more and 1150nm or less, 520nm or more and 1000nm or less, 520nm or more and 600nm or less.

[0218] The phase difference (Rth) in the thickness direction of the biaxially stretched plastic film is preferably 2000 nm or more, more preferably 3000 nm or more, and further preferably 4000 nm or more. The upper limit of Rth is about 10000 nm, preferably 8000 nm or less, and more preferably 7000 nm or less. By setting Rth to the above range, rainbow unevenness can be more easily suppressed.

[0219] Preferred ranges of Rth of the biaxially stretched plastic film include 2000 nm to 10000 nm, 2000 nm to 8000 nm, 2000 nm to 7000 nm, 3000 nm to 10000 nm, 3000 nm to 8000 nm, 3000 nm to 7000 nm, 4000 nm to 10000 nm, 4000 nm to 8000 nm, and 4000 nm to 7000 nm.

[0220] In order to make the Rth of the biaxially stretched plastic film within the above range, it is preferred to increase the longitudinal and transverse stretching ratios. By increasing the longitudinal and transverse stretching ratios, the refractive index nz in the thickness direction of the biaxially stretched plastic film becomes smaller, so it is easy to increase Rth. In addition, by reducing the nz of the biaxially stretched plastic film, it is easy to reduce the value of "(α+β) / 2". If the value of "(α+β) / 2" becomes smaller, the value of (α+β) / 2 moves away from the vicinity of the Brewster angle, so it is easy to suppress the change in the reflectivity of the P wave and the S wave at the angles before and after (α+β) / 2.

[0221] By setting the in-plane phase difference and the phase difference in the thickness direction to be within the above ranges, the stretching degree of the biaxially stretched plastic film can be made close to uniform biaxiality, and the mechanical strength of the biaxially stretched plastic film can be improved.

[0222] The in-plane phase difference (Re) and the phase difference in the thickness direction (Rth) are expressed by the following formulas (1) and (2) based on the refractive index nx in the slow axis direction, which is the direction in which the refractive index is the largest, the refractive index ny in the fast axis direction, which is the direction perpendicular to the slow axis direction, the refractive index nz in the thickness direction of the plastic film, and the thickness T [nm] of the plastic film. In this specification, the in-plane phase difference and the phase difference in the thickness direction refer to the values ​​at a wavelength of 550nm.

[0223] Re=(nx-ny)×T[nm] (1)

[0224] Rth=((nx+ny) / 2-nz)×T[nm] (2)

[0225] The direction of the slow axis, the in-plane phase difference, and the phase difference in the thickness direction can be measured, for example, by an instrument with the trade name “RETS-100” manufactured by Otsuka Electronics Co., Ltd.

[0226] When measuring the in-plane phase difference or the like using an instrument with a trade name of “RETS-100” manufactured by Otsuka Electronics Co., Ltd., it is preferable to prepare for the measurement according to the following steps (A1) to (A4).

[0227] (A1) First, in order to stabilize the light source of RETS-100, leave it for more than 60 minutes after installing the light source. Then, select the rotating analyzer method and select the θ mode (the mode for angular phase difference measurement and Rth calculation). By selecting this θ mode, the worktable becomes a tilting rotation worktable.

[0228] (A2) Next, the following measurement conditions are input into RETS-100.

[0229] (Measurement conditions)

[0230] Delay measurement range: rotating analyzer method

[0231] Measuring point diameter:

[0232] Tilt angle range: 0°

[0233] ·Measurement wavelength range: above 400nm and below 800nm

[0234] Average refractive index of the plastic film. For example, in the case of a PET film, N=1.617. The average refractive index N of the plastic film can be calculated based on nx, ny, and nz by the formula (N=(nx+ny+nz) / 3).

[0235] Thickness: Thickness measured separately using SEM or optical microscope

[0236] (A3) Next, background data is obtained without placing a sample in the device. The device is set as a closed system, and this setting is performed every time the light source is turned on.

[0237] (A4) Then, a sample is set on a stage within the device and measurement is performed.

[0238] Regarding the in-plane phase difference and the phase difference in the thickness direction, and the direction of the slow axis described later, it is preferred to cut a sample of 50 mm in length and 50 mm in width from the biaxially stretched plastic film, and set them as the average of the values ​​measured at 5 locations of the sample. The 5 measurement points are 1 location in the center and 4 locations at 10 mm from the four corners of the sample toward the center, for a total of 5 locations ( Figure 7 5 locations of the black dots).

[0239] The in-plane phase difference of the biaxially stretched plastic film relative to the phase difference in the thickness direction (in-plane phase difference / phase difference in the thickness direction) is preferably 0.10 or less. In this specification, "Re / Rth" is sometimes used to represent the in-plane phase difference relative to the phase difference in the thickness direction. Re / Rth can be measured, for example, as follows.

[0240] The in-plane phase differences measured at 5 locations of the above sample are defined as Re1, Re2, Re3, Re4 and Re5, respectively, and the phase differences in the thickness direction measured at 5 locations of the above sample are defined as Rth1, Rth2, Rth3, Rth4 and Rth5, respectively.

[0241] Regarding the biaxially stretched plastic film, it is preferred that the average value of Re1 / Rth1, Re2 / Rth2, Re3 / Rth3, Re4 / Rth4, and Re5 / Rth5 is 0.10 or less.

[0242] A small ratio of the in-plane phase difference to the phase difference in the thickness direction (Re / Rth) means that the biaxial stretching of the biaxially stretched plastic film is close to equal biaxiality. Therefore, by making Re / Rth 0.10 or less, the mechanical strength of the biaxially stretched plastic film can be improved. Re / Rth is more preferably 0.07 or less, and further preferably 0.05 or less. The lower limit of Re / Rth is about 0.01.

[0243] The Re / Rth of a completely uniaxially stretched plastic film is 2.0. A commonly used uniaxially stretched plastic film is also slightly stretched in the conveying direction. Therefore, the Re / Rth of a commonly used uniaxially stretched plastic film is about 1.0.

[0244] Re1 / Rth1, Re2 / Rth2, Re3 / Rth3, Re4 / Rth4 and Re5 / Rth5 are each preferably 0.10 or less, more preferably 0.07 or less, and still more preferably 0.05 or less. The lower limit of these ratios is about 0.01.

[0245] The biaxially stretched plastic film preferably satisfies the following condition 2.

[0246] <Condition 2>

[0247] The directions of the slow axis are measured at five locations of the sample. When the angles formed between any one side of the sample and the directions of the slow axis of each measurement location are defined as D1, D2, D3, D4, and D5, respectively, the difference between the maximum value of D1 to D5 and the minimum value of D1 to D5 is greater than 5.0 degrees.

[0248] If the slow axis of the biaxially stretched plastic film is uniformly oriented, there is a tendency for rainbow unevenness to be easily observed. On the other hand, if the slow axis of the biaxially stretched plastic film is given a deviation, the rainbow unevenness becomes blurred and difficult to observe. Therefore, by satisfying condition 2, it is easy to suppress the situation where the rainbow unevenness is observed by the naked eye. In other words, by satisfying condition 2, it is easy to satisfy that the difference between the maximum value and the minimum value of ΔEab is less than 17.0.

[0249] Commonly used stretched plastic films are designed so that the direction of the slow axis does not deviate. However, as described above, rainbow unevenness can be easily suppressed by deliberately deviating the direction of the slow axis of the plastic film. In addition, in a large area, even if the slow axis is scattered, the effect of suppressing rainbow unevenness is small, but in a relatively small area such as 50 mm in length and 50 mm in width, rainbow unevenness can be easily suppressed by scattering the slow axis.

[0250] In condition 2, any one side of the sample that serves as a reference for the angle formed with the slow axis direction may be any of the longitudinal side and the lateral side of the sample as long as the same side is used as a reference in all D1 to D5.

[0251] Furthermore, from the viewpoint of being able to improve the folding resistance of the biaxially stretched plastic film, it is preferable to satisfy condition 2.

[0252] On the other hand, the commonly used oriented films that do not satisfy condition 2 and have the same slow axis will cause the film to break after the bending test, or the bending tendency will remain strongly. Specifically, the uniaxially stretched film such as Patent Document 1 breaks when the bending test is performed along the slow axis, and the bending tendency remains strongly when the bending test is performed in a direction perpendicular to the slow axis. In addition, the commonly used biaxially stretched film has a strong bending tendency remaining when the bending test is performed in a direction perpendicular to the slow axis.

[0253] The biaxially stretched plastic film satisfying condition 2 is preferred in that it is possible to suppress the bending tendency from remaining or the occurrence of breakage after the bending test regardless of the bending direction.

[0254] The difference between the maximum value of D1 to D5 and the minimum value of D1 to D5 is preferably 6.0 degrees or more, more preferably 8.0 degrees or more, and further preferably 10.0 degrees or more.

[0255] If the difference between the maximum value of D1 to D5 and the minimum value of D1 to D5 is too large, the orientation of the plastic film tends to be reduced and the mechanical strength tends to be reduced. Therefore, the difference is preferably 20.0 degrees or less, more preferably 17.0 degrees or less, and further preferably 15.0 degrees or less.

[0256] In condition 2, the preferred range of the difference between the maximum value and the minimum value of D1 to D5 can be, for example, 5.0 degrees to 20.0 degrees, 6.0 degrees to 20.0 degrees, 8.0 degrees to 20.0 degrees, 10.0 degrees to 20.0 degrees, 5.0 degrees to 17.0 degrees, 6.0 degrees to 17.0 degrees, 8.0 degrees to 17.0 degrees, 10.0 degrees to 17.0 degrees, 5.0 degrees to 15.0 degrees, 6.0 degrees to 15.0 degrees, 8.0 degrees to 15.0 degrees, and 10.0 degrees to 15.0 degrees.

[0257] D1 to D5 of the biaxially stretched plastic film are preferably 5 to 30 degrees or 60 to 85 degrees, more preferably 7 to 25 degrees or 65 to 83 degrees, further preferably 10 to 23 degrees or 67 to 80 degrees.

[0258] By setting D1 to D5 to 5 degrees or more or 85 degrees or less, blackout when viewing with polarized sunglasses can be easily suppressed. In addition, by setting D1 to D5 to 30 degrees or less or 60 degrees or more, the reduction in mechanical strength due to the low orientation of the plastic film can be easily suppressed.

[0259] Biaxially stretched plastic films may be in the form of sheets or rolls. In either case, a sample of 50 mm in length and 50 mm in width may be cut out from any position of the plastic film, but in the case where the longitudinal and transverse directions of the sheet and roll can be confirmed, the sample is cut out along the confirmed longitudinal and transverse directions. For example, in the case of a roll, the conveying direction (MD direction) of the roll may be regarded as the longitudinal direction, and the width direction (TD direction) of the roll may be regarded as the transverse direction. In addition, in the case where the conveying direction and the width direction of the sheet can be confirmed, the conveying direction may be regarded as the longitudinal direction, and the width direction may be regarded as the transverse direction. In the case where it is difficult to confirm the conveying direction and the width direction of the sheet, if the sheet is a rectangle or a square, it is sufficient to confirm the longitudinal and transverse directions through the four sides constituting the rectangle or the square. In the case where it is difficult to confirm the conveying direction and the width direction of the sheet, if the sheet is a shape other than a rectangle or a square (circle, triangle, etc.), it is sufficient to draw a rectangle or a square with the largest area that does not extend from the outer frame shape of the sheet, and confirm the longitudinal and transverse directions through the sides of the drawn rectangle or square.

[0260] Furthermore, when a plurality of samples of 50 mm in length and 50 mm in width can be collected from a sheet of plastic film, the proportion of samples satisfying condition 2 among the plurality of samples is preferably 50% or more, more preferably 70% or more, further preferably 90% or more, and further preferably 100%. The same applies to the in-plane phase difference, the phase difference in the thickness direction, and Re / Rth.

[0261] The biaxially stretched plastic film preferably does not produce cracks or breaks after the folding test shown in the embodiment is performed 100,000 times (more preferably after 300,000 times). In addition, with respect to the biaxially stretched plastic film, it is preferred that after the folding test shown in the embodiment is performed 100,000 times (more preferably after 300,000 times), when the measurement sample is placed on a horizontal table, the angle at which the end of the sample is lifted up from the table is less than 20 degrees, more preferably less than 15 degrees. The fact that the end of the sample is lifted up at an angle of less than 15 degrees means that it is difficult to produce a tendency caused by folding. In addition, for any direction of the average in the direction of the slow axis and the average in the direction of the fast axis of the biaxially stretched plastic film, it is preferred to show the aforementioned results (no cracks, breaks, and tendencies caused by folding. The angle of lift at the end of the sample after the test is less than 20 degrees).

[0262] Furthermore, a uniaxially stretched plastic film will break in the stretching direction during a folding test, and will have a strong tendency to bend in a direction perpendicular to the stretching direction.

[0263] 《Specific composition of biaxially stretched plastic film》

[0264] The laminated structure of the biaxially stretched plastic film may be a single-layer structure or a multi-layer structure, of which a single-layer structure is preferred.

[0265] Regarding the biaxially stretched plastic film, in order to improve the mechanical strength and suppress rainbow unevenness, it is preferable to reduce the in-plane phase difference. In addition, in order to reduce the in-plane phase difference of the stretched plastic film, it is important to make the longitudinal and transverse stretching close to equal. Regarding fine stretching control, in a multilayer structure, it is difficult to perform fine stretching control due to the difference in physical properties of each layer, but a single-layer structure is preferred in that fine stretching control is easy.

[0266] As the resin component constituting the biaxially stretched plastic film, polyester, polyimide, polyethersulfone, polysulfone, polypropylene, polymethylpentene, polyvinyl chloride, polyvinyl acetal, polyetherketone, polymethyl methacrylate, polycarbonate, polyurethane and amorphous olefin (Cyclo-Olefin-Polymer: COP) etc. can be listed. Among them, polyester is preferred from the aspect of easy improvement of mechanical strength. That is, the biaxially stretched plastic film is preferably a polyester film, and more preferably a biaxially stretched polyethylene terephthalate film.

[0267] In order to obtain good mechanical strength, the biaxially stretched plastic film preferably satisfies n x >n y ≥n z In order to satisfy n x >n y ≥n z The relationship between the two is that the resin component constituting the biaxially stretched plastic film is preferably a positive birefringence material.

[0268] For satisfying n x >n y ≥n z The phase difference in the oblique direction of the biaxially stretched plastic film with the relationship of α and β gradually decreases as it tilts along the slow axis, and becomes 0 nm near "(α+β) / 2". As described above, "color distortion" is easily felt when the oblique phase difference is 0 nm when the elevation angle along the slow axis is "(α+β) / 2". In the present disclosure, even if n is used to satisfy the condition that color distortion is easily generated, x >n y ≥n zFor a biaxially stretched plastic film having a relationship of ΔEab, color distortion can be easily suppressed by making the difference between the maximum value and the minimum value of ΔEab less than 17.0.

[0269] Examples of the positive birefringence material include polyester, polycarbonate, cycloolefin polymer, polyimide film, and polyamide.

[0270] Examples of the polyester constituting the biaxially stretched polyester film include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), etc. Among them, PET is preferred because it has low intrinsic birefringence and is easy to reduce in-plane phase difference.

[0271] The biaxially stretched plastic film may contain additives such as an ultraviolet absorber, a light stabilizer, an antioxidant, an antistatic agent, a flame retardant, an anti-gelling agent, and a surfactant.

[0272] The lower limit of the thickness of the biaxially stretched plastic film is preferably 10 μm or more, more preferably 15 μm or more, more preferably 20 μm or more, more preferably 25 μm or more, more preferably 30 μm or more, and the upper limit is preferably 200 μm or less, more preferably 180 μm or less, more preferably 150 μm or less, more preferably 100 μm or less, more preferably 80 μm or less, more preferably 60 μm or less, more preferably 50 μm or less. In order to achieve thin film, the thickness of the biaxially stretched plastic film is preferably 50 μm or less.

[0273] By setting the thickness to be 10 μm or more, the mechanical strength can be easily improved, and by setting the thickness to be 200 μm or less, the in-plane phase difference can be easily reduced to 2500 nm or less.

[0274] The preferred range of the thickness of the biaxially stretched plastic film is, for example, 10 μm to 200 μm, 15 μm to 200 μm, 20 μm to 200 μm, 25 μm to 200 μm, 30 μm to 200 μm, 10 μm to 180 μm, 15 μm to 180 μm, 20 μm to 180 μm, 25 μm to 180 μm, 30 μm to 180 μm, 10 μm to 150 μm, 15 μm to 150 μm, 20 μm to 150 μm, 25 μm to 150 μm, 30 μm to 150 μm, 10 μm to 100 μm, 15 μm to 150 μm, and less than 100μm, 20μm or more and less than 100μm, 25μm or more and less than 100μm, 30μm or more and less than 100μm, 10μm or more and less than 80μm, 15μm or more and less than 80μm, 20μm or more and less than 80μm, 25μm or more and less than 80μm, 30μm or more and less than 80μm, 10μm or more and less than 60μm, 15μm or more and less than 60μm, 20μm or more and less than 60μm, 25μm or more and less than 60μm, 30μm or more and less than 60μm, 10μm or more and less than 50μm, 15μm or more and less than 50μm, 20μm or more and less than 50μm, 25μm or more and less than 50μm, 30μm or more and less than 50μm.

[0275] The haze of the biaxially stretched plastic film in accordance with JIS K7136:2000 is preferably 3.0% or less, more preferably 2.0% or less, further preferably 1.5% or less, and further preferably 1.0% or less.

[0276] The total light transmittance of the biaxially stretched plastic film according to JIS K7361-1:1997 is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more.

[0277] The biaxially stretched plastic film can be obtained by stretching a resin layer containing components constituting the plastic film. The stretching method includes sequential biaxial stretching and simultaneous biaxial stretching.

[0278] -Sequential biaxial stretching-

[0279] In the sequential biaxial stretching, after the cast film is stretched in the conveying direction, stretching in the width direction of the film is performed.

[0280] The stretching in the conveying direction is usually implemented by the difference in the peripheral speed of a pair of stretching rollers. The stretching in the conveying direction can be carried out in one stage, or it can be carried out in multiple stages using multiple stretching rollers. In order to suppress excessive deviations of optical properties such as in-plane phase difference, it is preferred to bring multiple clamping rollers close to the stretching rollers. The stretching ratio in the conveying direction is usually more than 2 times and less than 15 times. In order to suppress excessive deviations of optical properties such as in-plane phase difference, it is preferably more than 2 times and less than 7 times, more preferably more than 3 times and less than 5 times, and further preferably more than 3 times and less than 4 times.

[0281] In order to suppress excessive deviation of optical properties such as in-plane phase difference, the stretching temperature is preferably higher than the glass transition temperature of the resin and lower than the glass transition temperature + 100° C. In the case of PET, it is preferably higher than 70° C. and lower than 120° C., more preferably higher than 80° C. and lower than 110° C., and further preferably higher than 95° C. and lower than 110° C.

[0282] Regarding the stretching temperature, by rapidly heating the film, the stretching interval at low temperature is shortened, thereby there is a tendency for the average value of the in-plane phase difference to become smaller. On the other hand, by slowly heating the film, the stretching interval at low temperature is extended, thereby there is a tendency for the orientation to be improved, the average value of the in-plane phase difference to be increased, and the deviation of the slow axis to be reduced.

[0283] Furthermore, it is preferred to use a heater that generates turbulence when heating during stretching. By using wind containing turbulence for heating, a temperature difference is generated in a fine region within the film surface, and a fine deviation is generated on the orientation axis due to the temperature difference, so that condition 2 can be easily satisfied. In addition, by making the plastic film satisfy condition 2, the difference between the maximum value and the minimum value of ΔEab can be easily made less than 17.0.

[0284] In-line coating can also be used to impart lubricity, adhesion, antistatic properties, and other functions to the film stretched along the conveying direction. In addition, before in-line coating, surface treatments such as corona treatment, flame treatment, and plasma treatment can be performed as needed.

[0285] The coating film formed by in-line coating is an extremely thin coating film having a thickness of about 10 nm to 2000 nm (the coating film is stretched to be thinner by stretching). In this specification, such thin layers are not counted as the number of layers constituting the plastic film.

[0286] The stretching in the width direction is usually carried out by conveying the film in the width direction while holding the two ends of the film with a clamp using a tenter method. The stretching ratio in the width direction is usually more than 2 times and less than 15 times. In order to suppress excessive deviations of optical properties such as in-plane phase difference, it is preferably more than 2 times and less than 5 times, more preferably more than 3 times and less than 5 times, and further preferably more than 3 times and less than 4.5 times. In addition, it is preferred that the width stretching ratio is higher than the longitudinal stretching ratio.

[0287] The stretching temperature is preferably above the glass transition temperature of the resin and below the glass transition temperature + 120°C, and the temperature is preferably increased from the upstream to the downstream. Specifically, when the transverse stretching interval is divided into two equal parts, the difference between the upstream temperature and the downstream temperature is preferably 20°C or more, more preferably 30°C or more, further preferably 35°C or more, and further preferably 40°C or more. In addition, in the case of PET, the stretching temperature in the first stage is preferably 80°C or more and 120°C or less, more preferably 90°C or more and 110°C or less, and further preferably 95°C or more and 105°C or less.

[0288] In order to impart planarity and dimensional stability, the plastic film after being sequentially biaxially stretched as described above is preferably subjected to heat treatment in a tenter at a temperature above the stretching temperature and below the melting point. Specifically, in the case of PET, heat fixation is preferably performed in the range of 150°C to 255°C, more preferably 200°C to 250°C. In addition, in order to suppress excessive deviations in optical properties such as in-plane phase difference, additional stretching of 1% to 10% is preferably performed in the first half of the heat treatment.

[0289] After the plastic film is heat-treated, it is slowly cooled to room temperature and then rolled up. In addition, as needed, relaxation treatment can also be used during heat treatment and slow cooling. In order to suppress excessive deviations of optical properties such as in-plane phase difference, the relaxation rate during heat treatment is preferably 0.5% or more and 5% or less, more preferably 0.5% or more and 3% or less, more preferably 0.8% or more and 2.5% or less, and more preferably 1% or more and 2% or less. In addition, in order to suppress excessive deviations of optical properties such as in-plane phase difference, the relaxation rate during slow cooling is preferably 0.5% or more and 3% or less, more preferably 0.5% or more and 2% or less, more preferably 0.5% or more and 1.5% or less, and more preferably 0.5% or more and 1.0% or less. In order to make the planarity good, the temperature during slow cooling is preferably 80°C or more and 150°C or less, more preferably 90°C or more and 130°C or less, more preferably 100°C or more and 130°C or less, and more preferably 100°C or more and 120°C or less.

[0290] - Simultaneous biaxial stretching -

[0291] Simultaneous biaxial stretching is to introduce the cast film into a simultaneous biaxial tenter, hold both ends of the film with a clamp while conveying, and stretch it simultaneously and / or stepwise in the conveying direction and the width direction. As a simultaneous biaxial stretching machine, there are a pantograph type, a screw type, a drive motor type, and a linear motor type, but the drive motor type or the linear motor type that can arbitrarily change the stretch ratio and can perform relaxation treatment at any place is preferred.

[0292] The ratio of the simultaneous biaxial stretching is usually 6 times or more and 50 times or less in terms of area ratio. In order to suppress excessive deviations of optical properties such as in-plane phase difference, the area ratio is preferably 8 times or more and 30 times or less, more preferably 9 times or more and 25 times or less, further preferably 9 times or more and 20 times or less, and further preferably 10 times or more and 15 times or less. In the simultaneous biaxial stretching, it is preferred that the stretching ratio in the transmission direction and the stretching ratio in the width direction are within the range of 2 times or more and 15 times or less, and are adjusted in a manner to become the aforementioned area ratio.

[0293] In the case of simultaneous biaxial stretching, in order to suppress the orientation difference in the plane, it is preferable that the stretching ratio in the conveying direction and the width direction are substantially the same, and the stretching speed in the conveying direction and the width direction are also substantially the same.

[0294] In order to suppress excessive deviation of optical properties such as in-plane phase difference, the stretching temperature of the simultaneous biaxial stretching is preferably not less than the glass transition temperature of the resin and not more than the glass transition temperature + 120° C. In the case of PET, it is preferably not less than 80° C. and not more than 160° C., more preferably not less than 90° C. and not more than 150° C., and further preferably not less than 100° C. and not more than 140° C.

[0295] In order to impart flatness and dimensional stability, the film subjected to simultaneous biaxial stretching is preferably subjected to heat treatment in a heat fixing chamber in a tenter at a temperature above the stretching temperature and below the melting point. The conditions for the heat treatment are the same as those for the heat treatment after the sequential biaxial stretching.

[0296] <Low Refractive Index Layer>

[0297] The low refractive index layer has a function of improving the antireflection property of the optical film and making it easier to suppress rainbow unevenness when observed with the naked eye.

[0298] The light from the inside of the image display device toward the observer side is linearly polarized in the stage of passing through the polarizer, but after passing through the biaxially stretched plastic film, the polarization state of the linear polarization is disturbed and becomes a mixture of P waves and S waves. Moreover, since there is a difference between the reflectivity of the P wave and the reflectivity of the S wave, and the reflectivity difference is wavelength-dependent, it is conceivable that rainbow unevenness can be seen with the naked eye. Here, it can be imagined that in the case of having a low refractive index layer on the biaxially stretched plastic film, the aforementioned reflectivity difference can be reduced, so the rainbow unevenness can be easily suppressed. However, it is difficult to make the difference between the maximum and minimum values ​​of ΔEab fall within the range simply by forming a low refractive index layer on the commonly used biaxially stretched plastic film, so that the rainbow unevenness cannot be suppressed at a high level. In order to make the difference between the maximum and minimum values ​​of ΔEab easily fall within the range, as described above, it is preferred to give a deviation to the direction of the slow axis of the biaxially stretched plastic film.

[0299] The low refractive index layer is preferably formed on the side of the optical film farthest from the biaxially stretched plastic film. Furthermore, by forming a high refractive index layer described later adjacent to the low refractive index layer on the biaxially stretched plastic film side relative to the low refractive index layer, the antireflection property can be further improved and rainbow unevenness can be more easily suppressed.

[0300] The refractive index of the low refractive index layer is preferably 1.10 to 1.48, more preferably 1.20 to 1.45, more preferably 1.26 to 1.40, more preferably 1.28 to 1.38, and more preferably 1.30 to 1.32.

[0301] In addition, the thickness of the low-refractive index layer is preferably 80 nm or more and 120 nm or less, more preferably 85 nm or more and 110 nm or less, more preferably 90 nm or more and 105 nm or less. In addition, the thickness of the low-refractive index layer is preferably greater than the average particle diameter of low-refractive index particles such as hollow particles.

[0302] As a method for forming a low refractive index layer, it can be roughly divided into a wet method and a dry method. As a wet method, a method of forming by a sol-gel method using a metal alkoxide or the like, a method of forming by coating a low refractive index resin such as a fluororesin, and a method of forming by coating a low refractive index layer containing low refractive index particles in a resin composition. As a dry method, the following method can be cited: selecting particles with a desired refractive index from the low refractive index particles described later, and forming by a physical vapor deposition method or a chemical vapor deposition method.

[0303] The wet method is superior to the dry method in terms of production efficiency, suppression of oblique reflection hue, and chemical resistance. In addition, in the wet method, for the purpose of adhesion, water resistance, scratch resistance, and low refractive index, it is preferably formed by using a coating liquid for forming a low refractive index layer containing low refractive index particles in a binder resin composition.

[0304] The low refractive index layer is usually located on the outermost surface of the optical film. Therefore, the low refractive index layer is required to have good scratch resistance, and the commonly used low refractive index layer is also designed to have a predetermined scratch resistance.

[0305] In recent years, in order to reduce the refractive index of the low refractive index layer, hollow particles with large particle size are used as low refractive index particles. The inventors have found the following problem (hereinafter, this problem is sometimes referred to as "oil dust resistance"): Even when no damage is observed when the surface of the low refractive index layer containing hollow particles with large particle size is rubbed with an object only attached with fine solid matter (such as sand) or an object only attached with oil, damage will occur when rubbing with an object attached with both solid matter and oil. The action of wiping with an object attached with solid matter and oil is equivalent to the action of a user operating a touch panel type image display device with a finger attached with oil contained in cosmetics and food, etc. and sand contained in the atmosphere.

[0306] It is preferable to improve the oil dust resistance of the low refractive index layer in order to maintain the rainbow unevenness suppression effect for a long period of time.

[0307] The inventors have studied and found that the above-mentioned damage is mainly caused by a part of the hollow particles contained in the low refractive index layer being defective or the hollow particles falling off. As the reason, it is considered that the concavoconvex caused by the hollow particles formed on the surface of the low refractive index layer is larger. That is, when wiping the surface of the low refractive index layer with a finger attached with solids and oil, the oil becomes an adhesive, and under the state that the solid is attached to the finger, the finger moves on the surface of the low refractive index layer. At this time, it can be imagined that: the phenomenon that a part of the solid (such as the sharp part of sand) easily produces enters the concave portion of the low refractive index layer surface and the solid that enters the concave portion passes through the concave portion and crosses the convex portion (hollow particles) together with the finger, and now a larger force can be applied to the convex portion (hollow particles), so the hollow particles can be damaged or fall off. In addition, it can be imagined that the resin itself located in the concave portion is also damaged due to the friction of the solid, and the hollow particles are more likely to fall off due to the damage of the resin.

[0308] The present inventors have conducted intensive studies and have found that, in order to impart oil dust resistance, it is effective to use both hollow particles and non-hollow particles as low-refractive index particles and to uniformly disperse the hollow particles and the non-hollow particles. Figure 8 A cross-sectional photograph showing a low refractive index layer in which hollow particles and non-hollow particles are uniformly dispersed, Fig. 9 A cross-sectional photograph of a low refractive index layer in which hollow particles and non-hollow particles are not uniformly dispersed is shown. Figure 8 and Fig. 9The cross-sectional photograph was obtained by observation using an electron microscope "Model: H-7650" manufactured by Hitachi High-Techn Corporation under the conditions of an emission current of 10 μA, an acceleration voltage of 100 keV, and a filament voltage of 20 V.

[0309] In order to improve the oil dust resistance, the low refractive index particles preferably include hollow particles and non-hollow particles.

[0310] The material of the hollow particles and the non-hollow particles can be any of inorganic compounds such as silica and magnesium fluoride, and organic compounds, but silica is preferred for lowering the refractive index and increasing strength. The following description will focus on hollow silica particles and non-hollow silica particles.

[0311] Hollow silica particles refer to particles that have an outer shell layer composed of silica, and the inside of the particles surrounded by the outer shell layer is hollow, and air is contained in the hollow. Hollow silica particles are particles whose refractive index is reduced in proportion to the occupancy rate of gas compared with the original refractive index of silica by containing air. Non-hollow silica particles refer to particles that are not hollow inside like hollow silica particles. Non-hollow silica particles are, for example, solid silica particles.

[0312] The shapes of the hollow silica particles and non-hollow silica particles are not particularly limited, and may be substantially spherical shapes such as true spheres, rotational ellipsoids, and polyhedrons that can approximate spheres. Of these, true spheres, rotational ellipsoids, or substantially spherical shapes are preferred in consideration of scratch resistance.

[0313] Hollow silica particles contain air inside, so they play a role in reducing the refractive index of the entire low refractive index layer. By using hollow silica particles with a large particle size that has improved the air ratio, the refractive index of the low refractive index layer can be further reduced. On the other hand, hollow silica particles have a tendency to deteriorate in mechanical strength. Especially in the case of hollow silica particles with a large particle size that has improved the air ratio, there is a tendency to easily reduce the scratch resistance of the low refractive index layer.

[0314] The non-hollow silica particles play a role in improving the scratch resistance of the low refractive index layer by being dispersed in the binder resin.

[0315] In order to make the binder resin contain hollow silica particles and non-hollow silica particles at a high concentration and make the particles uniformly dispersed in the resin along the film thickness direction, it is preferred to set the average particle size of the hollow silica particles and the average particle size of the non-hollow silica particles in a manner that the hollow silica particles are close to each other and the non-hollow particles enter the hollow silica particles. Specifically, the ratio of the average particle size of the non-hollow silica particles to the average particle size of the hollow silica particles (average particle size of the non-hollow silica particles / average particle size of the hollow silica particles) is preferably less than 0.29, more preferably less than 0.27. In addition, the ratio of the average particle size is preferably more than 0.05, more preferably more than 0.10.

[0316] Taking into account optical properties and mechanical strength, the average particle size of the hollow silica particles is preferably 20 nm or more and 100 nm or less. In order to easily reduce the refractive index of the low refractive index layer as a whole, the average particle size of the hollow silica particles is more preferably 50 nm or more and 100 nm or less, and more preferably 60 nm or more and 80 nm or less. In addition, if the dispersion is considered while preventing the agglomeration of the non-hollow silica particles, the average particle size of the non-hollow silica particles is preferably 5 nm or more and 20 nm or less, and more preferably 10 nm or more and 15 nm or less.

[0317] It is preferred that the hollow silica particles and non-hollow silica particles have their surfaces coated with a silane coupling agent, and it is more preferred to use a silane coupling agent having a (meth)acryloyl group or an epoxy group.

[0318] By subjecting the silica particles to a surface treatment using a silane coupling agent, the affinity between the silica particles and the binder resin is improved, and aggregation of the silica particles is less likely to occur. Therefore, the silica particles are easily dispersed uniformly.

[0319] Examples of the silane coupling agent include 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-Triethoxysilyl-N-(1,3-dimethyl-butylene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, tris-(trimethoxysilylpropyl)isocyanurate, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isopropyltriethoxysilane, methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, 1,6-bis(trimethoxysilyl)hexane, trifluoropropyltrimethoxysilane, vinyltrimethoxysilane, and vinyltriethoxysilane. It is particularly preferable to use one or more selected from 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, and 3-methacryloxypropyltriethoxysilane.

[0320] The more the content of the hollow silica particles, the higher the filling rate of the hollow silica particles in the binder resin, and the lower the refractive index of the low refractive index layer. Therefore, relative to 100 parts by mass of the binder resin, the content of the hollow silica particles is preferably 100 parts by mass or more, more preferably 125 parts by mass or more.

[0321] On the other hand, when the content of the hollow silica particles relative to the binder resin is too much, the hollow silica particles exposed from the binder resin increase, and the binder resin that binds the particles becomes less. Therefore, the hollow silica particles are easily damaged or fall off, and there is a tendency that the mechanical strength such as the scratch resistance of the low refractive index layer is reduced. Therefore, relative to 100 parts by mass of the binder resin, the content of the hollow silica particles is preferably less than 400 parts by mass, more preferably less than 300 parts by mass, and further preferably less than 200 parts by mass.

[0322] If the content of non-hollow silica particles is small, even if non-hollow silica particles are present on the surface of the low refractive index layer, sometimes the hardness rise will not be affected. In addition, if a large amount of non-hollow silica particles are contained, the impact of the shrinkage unevenness caused by the polymerization of the binder resin can be reduced, so that the concavo-convex produced on the surface of the low refractive index layer after the resin is cured can be reduced. Therefore, the content of non-hollow silica particles is preferably more than 20 mass parts relative to 100 mass parts of binder resin, more preferably more than 40 mass parts, more preferably more than 90 mass parts, and more preferably more than 100 mass parts.

[0323] On the other hand, if the content of non-hollow silica particles is too much, the non-hollow silica is easily condensed, resulting in uneven shrinkage of the binder resin and larger surface concavities. Therefore, relative to 100 parts by mass of the binder resin, the content of the non-hollow silica particles is preferably 200 parts by mass or less, more preferably 150 parts by mass or less, and further preferably 120 parts by mass or less.

[0324] By including hollow silica particles and non-hollow silica particles in the binder resin at the above ratio, the barrier properties of the low refractive index layer can be improved. This is presumably because the silica particles are uniformly dispersed at a high filling rate, thereby inhibiting the permeation of gas or the like.

[0325] In addition, various cosmetics such as sunscreen and hand cream sometimes contain low-molecular polymers with low volatility. By making the barrier property of the low refractive index layer good, it is possible to inhibit the low molecular polymer from penetrating into the coating film of the low refractive index layer, thereby inhibiting the undesirable conditions (such as abnormal appearance) caused by the low molecular polymer remaining in the coating film for a long time.

[0326] The binder resin of the low refractive index layer preferably comprises a cured product of an ionizing radiation curable resin composition. In addition, as the ionizing radiation curable compound contained in the ionizing radiation curable resin composition, a compound having an ethylenically unsaturated bond group is preferred. Among them, a (meth)acrylate compound having a (meth)acryloyl group is more preferred.

[0327] Hereinafter, a (meth)acrylate compound having 4 or more ethylenically unsaturated bond groups is referred to as a "multifunctional (meth)acrylate compound". In addition, a (meth)acrylate compound having 2 or more and 3 or less ethylenically unsaturated bond groups is referred to as a "low-functional (meth)acrylate compound".

[0328] As the (meth)acrylate compound, any of a monomer and an oligomer can be used. In particular, in order to suppress uneven shrinkage during curing and to facilitate smoothing of the concavo-convex shape of the low refractive index layer surface, the ionizing radiation curable compound more preferably includes a low-functional (meth)acrylate compound.

[0329] The proportion of the low-functional (meth)acrylate compound in the ionizing radiation-curable compound is preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, further preferably 95% by mass or more, and most preferably 100% by mass.

[0330] In order to suppress the shrinkage unevenness during curing and to make the unevenness of the surface of the low refractive index layer smooth, the low-functional (meth)acrylate compound is preferably a (meth)acrylate compound having two ethylenically unsaturated bond groups.

[0331] Among the (meth)acrylate compounds, examples of bifunctional (meth)acrylate compounds include isocyanuric acid di(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol diacrylate, polybutylene glycol di(meth)acrylate and other polyalkylene glycol di(meth)acrylates, bisphenol A tetraethoxy diacrylate, bisphenol A tetrapropoxy diacrylate, 1,6-hexanediol diacrylate and the like.

[0332] Examples of the trifunctional (meth)acrylate compound include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and isocyanuric acid-modified tri(meth)acrylate.

[0333] Examples of the tetrafunctional or higher polyfunctional (meth)acrylate-based compounds include pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and dipentaerythritol tetra(meth)acrylate.

[0334] These (meth)acrylate compounds may be modified as described below.

[0335] Examples of the (meth)acrylate oligomer include acrylate polymers such as urethane (meth)acrylate, epoxy (meth)acrylate, polyester (meth)acrylate, and polyether (meth)acrylate.

[0336] Urethane (meth)acrylate can be obtained by reaction of, for example, a polyol and an organic diisocyanate with a hydroxy (meth)acrylate.

[0337] In addition, preferred epoxy (meth)acrylates are (meth)acrylates obtained by reacting trifunctional or higher aromatic epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, etc. with (meth)acrylic acid, (meth)acrylates obtained by reacting difunctional or higher aromatic epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, etc. with polybasic acids and (meth)acrylic acid, and (meth)acrylates obtained by reacting difunctional or higher aromatic epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, etc. with phenols and (meth)acrylic acid.

[0338] In addition, in order to suppress the uneven shrinkage caused by cross-linking and improve the smoothness of the surface, the above-mentioned (meth) acrylate compound can also be a compound modified by modifying a part of the molecular skeleton. For example, as the above-mentioned (meth) acrylate compound, a compound modified by using ethylene oxide, propylene oxide, caprolactone, isocyanuric acid, alkyl, cyclic alkyl, aromatic, bisphenol, etc. can also be used. In particular, in order to improve the affinity with low-refractive index particles (silicon dioxide particles therein) and suppress the aggregation of low-refractive index particles, the above-mentioned (meth) acrylate compound is preferably a compound modified by using alkylene oxides such as ethylene oxide and propylene oxide.

[0339] The proportion of the alkylene oxide-modified (meth)acrylate compound in the ionizing radiation curable compound is preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, further preferably 95% by mass or more, and most preferably 100% by mass. In addition, the alkylene oxide-modified (meth)acrylate compound is preferably a low-functional (meth)acrylate compound, more preferably a (meth)acrylate compound having two ethylenically unsaturated bond groups.

[0340] As the (meth)acrylate compound having two ethylenically unsaturated bond groups obtained by alkylene oxide modification, bisphenol F alkylene oxide modified di(meth)acrylate, bisphenol A alkylene oxide modified di(meth)acrylate, isocyanuric acid alkylene oxide modified di(meth)acrylate and polyalkylene glycol di(meth)acrylate can be cited, among which polyalkylene glycol di(meth)acrylate is preferred. The average repeating unit of the alkylene glycol contained in the polyalkylene glycol di(meth)acrylate is preferably 3 or more and 5 or less. In addition, the alkylene glycol contained in the polyalkylene glycol di(meth)acrylate is preferably ethylene glycol and / or polyethylene glycol.

[0341] Examples of the (meth)acrylate compound having three ethylenically unsaturated bond groups that has been modified with an alkylene oxide include trimethylolpropane alkylene oxide-modified tri(meth)acrylate and isocyanuric acid alkylene oxide-modified tri(meth)acrylate.

[0342] The above-mentioned ionizing radiation curable resins can be used alone or in combination of two or more.

[0343] The low refractive index layer preferably contains a leveling agent for the purpose of improving antifouling properties and surface smoothness.

[0344] As for the leveling agent, fluorine-based and silicone-based agents can be cited, and silicone-based agents are preferred. By containing a silicone-based leveling agent, the surface of the low reflectivity layer can be made smoother. Furthermore, the sliding property and antifouling property (fingerprint wiping property, large contact angle relative to pure water and hexadecane) of the surface of the low reflectivity layer can be improved.

[0345] The content of the leveling agent is preferably 1 part by mass or more and 25 parts by mass or less, more preferably 2 parts by mass or more and 20 parts by mass or less, and further preferably 5 parts by mass or more and 18 parts by mass or less relative to 100 parts by mass of the binder resin. By making the content of the leveling agent 1 part by mass or more, various properties such as antifouling properties can be easily imparted. In addition, by making the content of the leveling agent 25 parts by mass or less, the reduction of scratch resistance can be suppressed.

[0346] The maximum height roughness Rz of the low refractive index layer is preferably below 110nm, more preferably below 90nm, further preferably below 70nm, and further preferably below 60nm. In addition, Rz / Ra (Ra is the arithmetic mean roughness) is preferably below 12.0, more preferably below 10.0. In the case where Rz is as large as above 90nm and below 110nm, it is particularly effective to set Rz / Ra to the aforementioned range.

[0347] In this specification, Ra and Rz are obtained by expanding the roughness of the two-dimensional roughness parameter described in the Scanning Probe Microscope SPM-9600 Upgrade Kit Operating Instructions (SPM-9600 February 2016, P.194-195) of Shimadzu Corporation into three-dimensional values. Ra and Rz are defined as follows.

[0348] (Arithmetic mean roughness Ra)

[0349] Only the reference length (L) is extracted from the roughness curve in the direction of its average line, the X-axis is taken in the direction of the average line of the extracted part, and the Y-axis is taken in the direction of the longitudinal magnification. The roughness curve is represented by y=f(x). At this time, it is calculated by the following formula.

[0350] [Formula 1]

[0351]

[0352] (Maximum height roughness Rz)

[0353] This value is obtained by extracting only a reference length from the roughness curve in the direction of its average line and measuring the interval between the top line and the bottom line of the valley of the extracted portion in the direction of the longitudinal magnification of the roughness curve.

[0354] When using a scanning probe microscope SPM-9600 manufactured by SHIMADZU CORPORATION, it is preferred to measure and analyze Ra and Rz under the following conditions, for example.

[0355] <Measurement conditions>

[0356] Measurement Mode: Phase

[0357] Scanning range: 5μm×5μm

[0358] Scan speed: 0.8Hz or more and 1Hz or less

[0359] Number of pixels: 512×512

[0360] Cantilever used: Product number “NCHR” of Nano World Holding AG, resonance frequency: 320 kHz, spring constant: 42 N / m

[0361] <Analysis conditions>

[0362] Tilt Correction: Line Fit

[0363] A small Rz means that the convex portion caused by the hollow silica particles in the micro region is small. In addition, a small Rz / Ra means that the concavity and convexity caused by the silica particles in the micro region are uniform and do not have concavities and convexities that are prominent relative to the average altitude difference of the concavity and convexity. In addition, in the present disclosure, the value of Ra is not particularly limited, and Ra is preferably 15 nm or less, more preferably 12 nm or less, further preferably 10 nm or less, and further preferably 6.5 nm or less.

[0364] The above-mentioned ranges of Rz and Rz / Ra can be easily satisfied by uniformly dispersing the low-refractive index particles in the low-refractive index layer or suppressing uneven shrinkage of the low-refractive index layer.

[0365] By making Rz and Rz / Ra on low refractive index layer surface be above-mentioned scope, it is possible to reduce the resistance when solid matter crosses the convex part (by being present in the hollow silica particles near the surface) on low refractive index layer surface. Therefore, it is conceivable that: even if load is applied while rubbing with the gravel with oil content, solid matter also can move smoothly on low refractive index layer surface. In addition, it is considered that the hardness of recess itself has also been improved. As a result, it is possible to infer: prevent the breakage or coming off of hollow silica particles, also prevent the damage of binder resin itself.

[0366] Unless otherwise specified, surface roughness such as Rz and Ra refers to the average value of 14 measurement points excluding the minimum and maximum values ​​among the 16 measurement points.

[0367] In this specification, regarding the 16 measurement locations, it is preferred that an area 0.5 cm from the outer edge of the measurement sample is used as a blank, and lines are drawn that divide the area inside the blank into five equal parts in the longitudinal and transverse directions, and the 16 intersections at this time are used as the measurement centers. The measurement sample is preferably 5 cm×5 cm.

[0368] The low refractive index layer can be formed by applying a low refractive index layer to form a coating solution and drying, wherein the low refractive index layer forms a coating solution by dissolving or dispersing the components constituting the low refractive index layer. Usually, in the low refractive index layer forming coating solution, a solvent is used in order to adjust the viscosity or to dissolve or disperse the components.

[0369] Examples of the solvent include ketones (acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.), ethers (dioxane, tetrahydrofuran, etc.), aliphatic hydrocarbons (hexane, etc.), alicyclic hydrocarbons (cyclohexane, etc.), aromatic hydrocarbons (toluene, xylene, etc.), halogenated carbons (dichloromethane, dichloroethane, etc.), esters (methyl acetate, ethyl acetate, butyl acetate, etc.), alcohols (butanol, cyclohexanol, etc.), cellosolves (methyl cellosolve, ethyl cellosolve, etc.), cellosolve acetates, sulfoxides (dimethyl sulfoxide, etc.), glycol ethers (1-methoxy-2-propyl acetate, etc.), amides (dimethylformamide, dimethylacetamide, etc.), and mixtures thereof may also be mentioned.

[0370] In the case where the volatilization of the solvent is too fast, when the low refractive index layer is formed with a coating liquid and dried, the solvent is violently convected. Therefore, even if the silicon dioxide particles in the coating liquid are in a uniformly dispersed state, it is also easy to destroy the uniformly dispersed state due to the violent convection of the solvent during drying. Therefore, as a solvent, it is preferred to include a solvent with a slow evaporation rate. Specifically, it is preferred to include a solvent with a relative evaporation rate (relative evaporation rate when the evaporation rate of n-butyl acetate is set to 100) of less than 70, more preferably including a solvent of more than 30 and less than 60. In addition, the relative evaporation rate is preferably more than 10 mass % and less than 50 mass % of all solvents, preferably more than 20 mass % and less than 40 mass %.

[0371] Examples of the relative evaporation rates of solvents having a slow evaporation rate include isobutyl alcohol (64), 1-butanol (47), 1-methoxy-2-propyl acetate (44), ethyl cellosolve (38), and cyclohexanone (32).

[0372] Furthermore, the remaining components of the solvent (solvents other than the solvent with a slow evaporation rate) are preferably excellent in solubility of the resin. In addition, the remaining part of the solvent is preferably a component with a relative evaporation rate of 100 or more.

[0373] In addition, in order to suppress the convection of the solvent during drying and improve the dispersibility of the silica particles, the drying temperature during the formation of the low refractive index layer is preferably as low as possible. The drying temperature can be appropriately set in consideration of the type of solvent, the dispersibility of the silica particles, the production speed, etc.

[0374] <Reflectivity>

[0375] The optical film of the present disclosure has a reflectance measured from the low refractive index layer side of preferably 2.00% or less, 1.70% or less, more preferably 1.20% or less, and further preferably 1.00% or less.

[0376] In this specification, the reflectance refers to the visual reflectance Y value of the CIE 1931 standard color system. The reflectance is preferably calculated as an average value of arbitrary 10 points.

[0377] In addition, in this specification, the reflectivity of the optical film is measured as follows: a sample is prepared by bonding a black plate to the side of the optical film opposite to the reflectivity measurement surface via a transparent adhesive layer, and light is incident from the low refractive index layer side of the sample at an incident angle of 5° for measurement. The light source for measuring the reflectivity is preferably a C light source.

[0378] The difference in refractive index between the component of the sample that contacts the transparent adhesive layer (e.g., a biaxially stretched plastic film) and the transparent adhesive layer is preferably set to within 0.15, more preferably within 0.10, more preferably within 0.05, and more preferably within 0.01. In addition, the black board is preferably a black board having a total light transmittance of 1% or less according to JIS K7361-1:1997, and more preferably a black board having a total light transmittance of 0% according to JIS K7361-1:1997. In addition, the difference in refractive index between the refractive index of the resin constituting the black board and the transparent adhesive layer is preferably set to within 0.15, more preferably within 0.10, more preferably within 0.05, and more preferably within 0.01.

[0379] <Haze, total light transmittance>

[0380] The haze of the optical film in accordance with JIS K7136:2000 is preferably 5% or less, more preferably 4% or less, and further preferably 3% or less. The haze of the optical film in accordance with JIS K7136:2000 is preferably 0.5% or more, more preferably 1.0% or more, and further preferably 1.5% or more.

[0381] The total light transmittance of the optical film in accordance with JIS K7361-1:1997 is preferably 90% or more, more preferably 91% or more, and even more preferably 92% or more.

[0382] <Other layers>

[0383] The optical film disclosed herein may also have other layers in addition to the biaxially stretched plastic film and the low refractive index layer. Furthermore, the low refractive index layer and other layers in addition to the low refractive index layer are preferably optically isotropic. The layer having optical isotropy refers to a layer having an in-plane phase difference of less than 20 nm, preferably less than 10 nm, and more preferably less than 5 nm.

[0384] For example, the optical film of the present disclosure preferably has one or more layers selected from a hard coat layer, an antiglare layer, and a high refractive index layer between the biaxially stretched plastic film and the low refractive index layer.

[0385] 《High refractive index layer》

[0386] The high refractive index layer is formed closer to the biaxially stretched plastic film than the low refractive index layer as required. In addition, when a hard coat layer described below is provided, the high refractive index layer is preferably formed between the hard coat layer and the low refractive index layer.

[0387] The refractive index of the high refractive index layer is preferably 1.53 to 1.85, more preferably 1.54 to 1.80, more preferably 1.55 to 1.75, and more preferably 1.56 to 1.70.

[0388] The thickness of the high refractive index layer is preferably 200 nm or less, more preferably 50 nm or more and 180 nm or less, and further preferably 70 nm or more and 150 nm or less. In the case of a high refractive index hard coat layer, the thickness of the hard coat layer is preferably used as a reference.

[0389] The high refractive index layer can be formed, for example, from a high refractive index layer-forming coating liquid containing a binder resin composition and high refractive index particles. Examples of the binder resin composition include the curable resin composition exemplified in the hard coat layer described below.

[0390] Examples of high refractive index particles include antimony pentoxide, zinc oxide, titanium oxide, cerium oxide, tin-doped indium oxide, antimony-doped tin oxide, yttrium oxide, and zirconium oxide. The refractive index of antimony pentoxide is about 1.79, the refractive index of zinc oxide is about 1.90, the refractive index of titanium oxide is about 2.3 to 2.7, the refractive index of cerium oxide is about 1.95, the refractive index of tin-doped indium oxide is about 1.95 to 2.00, the refractive index of antimony-doped tin oxide is about 1.75 to 1.85, the refractive index of yttrium oxide is about 1.87, and the refractive index of zirconium oxide is 2.10.

[0391] The average particle diameter of the high refractive index particles is preferably more than 2nm, more preferably more than 5nm, and further preferably more than 10nm. In addition, in order to suppress whitening and achieve transparency, the average particle diameter of the high refractive index particles is preferably less than 200nm, more preferably less than 100nm, more preferably less than 80nm, more preferably less than 60nm, and more preferably less than 30nm. The smaller the average particle diameter of the high refractive index particles, the better the transparency, and in particular, by being set to less than 60nm, the transparency can be made extremely good.

[0392] The average particle size of the high refractive index particles or the low refractive index particles can be calculated by the following operations (y1) to (y3).

[0393] (y1) Photographing a cross section of the high refractive index layer or the low refractive index layer using TEM or STEM The acceleration voltage of TEM or STEM is preferably set to 10 kV or more and 30 kV or less, and the magnification is preferably set to 50,000 or more and 300,000 or less.

[0394] (y2) Ten random particles are extracted from the observed image, and the particle size of each particle is calculated. The particle size is measured as the distance between two random parallel straight lines in the combination of two straight lines that is the largest when the cross section of the particle is sandwiched between the two straight lines. In the case of particle aggregation, the aggregated particles are measured as one particle.

[0395] (y3) The same operation is performed five times on observation images of the same sample in different screens, and the value obtained by the number average of the particle sizes of 50 particles in total is taken as the average particle size of the high refractive index particles or the low refractive index particles.

[0396] Hard coating

[0397] In order to improve the scratch resistance of the optical film, a hard coating is formed as required. The hard coating is preferably formed between the biaxially stretched plastic film and the low refractive index layer. In addition, when the optical film further has a high refractive index layer, the hard coating, the high refractive index layer and the low refractive index layer are preferably sequentially arranged on the biaxially stretched plastic film.

[0398] In order to improve the scratch resistance, the hard coat layer preferably contains a cured product of a curable resin composition such as a thermosetting resin composition or an ionizing radiation curable resin composition, and more preferably contains a cured product of an ionizing radiation curable resin composition.

[0399] Thermosetting resin composition is a composition containing at least a thermosetting resin and is a resin composition that is cured by heating. Examples of thermosetting resins include acrylic resins, polyurethane resins, phenolic resins, urea melamine resins, epoxy resins, unsaturated polyester resins, silicone resins, and the like. For thermosetting resin compositions, a curing agent is added to these curable resins as required.

[0400] Ionizing radiation curable resin composition is a composition containing a compound having an ionizing radiation curable functional group (hereinafter, also referred to as "ionizing radiation curable compound"). As the ionizing radiation curable functional group, ethylenically unsaturated bond groups such as (meth) acryloyl, vinyl, allyl, and epoxy, oxetane, etc. can be listed. As the ionizing radiation curable compound, a compound having an ethylenically unsaturated bond group is preferred, and a compound having more than two ethylenically unsaturated bond groups is more preferred, wherein, a (meth) acrylate compound having more than two ethylenically unsaturated bond groups is further preferred. As a (meth) acrylate compound having more than two ethylenically unsaturated bond groups, any one of a monomer and an oligomer can be used.

[0401] Furthermore, ionizing radiation refers to radiation in electromagnetic waves or charged particle beams that has an energy quantum capable of polymerizing or cross-linking molecules, and is usually ultraviolet (UV) or electron beam (EB). In addition, electromagnetic waves such as X-rays and gamma rays, and charged particle beams such as alpha rays and ion rays may also be used.

[0402] In the present specification, (meth)acrylate means acrylate or methacrylate, (meth)acrylic acid means acrylic acid or methacrylic acid, and (meth)acryloyl means acryloyl or methacryloyl.

[0403] In order to achieve good scratch resistance, the thickness of the hard coating layer is preferably 0.1 μm or more, more preferably 0.5 μm or more, further preferably 1.0 μm or more, and further preferably 2.0 μm or more. In addition, in order to suppress curling, the thickness of the hard coating layer is preferably 100 μm or less, more preferably 50 μm or less, more preferably 30 μm or less, more preferably 20 μm or less, more preferably 15 μm or less, and more preferably 10 μm or less. In order to achieve good bending resistance, the thickness of the hard coating layer is preferably 10 μm or less, and more preferably 8 μm or less.

[0404] Anti-glare layer

[0405] The anti-glare layer can be formed from, for example, an anti-glare layer-forming coating liquid containing a binder resin composition and particles. As the binder resin composition, for example, the curable resin composition exemplified in the hard coat layer can be used.

[0406] The particles may be either organic particles or inorganic particles. Examples of organic particles include particles made of polymethyl methacrylate, polyacrylic acid-styrene copolymer, melamine resin, polycarbonate, polystyrene, polyvinyl chloride, benzoguanamine-melamine-formaldehyde condensate, silicone, fluorine resin, and polyester resin. Examples of inorganic particles include particles made of silicon dioxide, aluminum oxide, antimony, zirconium oxide, and titanium dioxide.

[0407] The average particle size of the particles in the antiglare layer cannot be generally determined because it varies depending on the thickness of the antiglare layer, but is preferably 1.0 μm to 10.0 μm, more preferably 2.0 μm to 8.0 μm, and further preferably 3.0 μm to 6.0 μm.

[0408] The average particle size of the particles in the antiglare layer can be calculated by the following operations (z1) to (z3).

[0409] (z1) Taking a transmission observation image of the cross section of the anti-glare layer using an optical microscope. The magnification is preferably 500 times or more and 2000 times or less.

[0410] (z2) Extract 10 random particles from the observed image and calculate the particle size of each particle. The particle size is measured as the distance between two random parallel straight lines in the combination of two straight lines that is the largest when the cross section of the particle is sandwiched between the two straight lines.

[0411] (z3) The same operation is repeated five times on observation images of different screens of the same sample, and the value obtained by the number average of 50 particle diameters is taken as the average particle diameter of the particles in the antiglare layer.

[0412] The content of particles in the anti-glare layer varies depending on the degree of the target anti-glare property and therefore cannot be generalized; however, it is preferably from 1 part by mass to 100 parts by mass, more preferably from 5 parts by mass to 50 parts by mass, and further preferably from 10 parts by mass to 30 parts by mass, relative to 100 parts by mass of the resin component.

[0413] Furthermore, the anti-glare layer may contain fine particles having an average particle size of less than 500 nm in order to impart antistatic properties, control the refractive index, or adjust the shrinkage of the anti-glare layer caused by curing of the curable resin composition.

[0414] The thickness of the anti-glare layer is preferably 0.5 μm or more, more preferably 1.0 μm or more, and further preferably 2.0 μm or more. In addition, the thickness of the anti-glare layer is preferably 50 μm or less, more preferably 30 μm or more, more preferably 20 μm or less, more preferably 15 μm or less, and more preferably 10 μm or less. In order to make the bending resistance good, the thickness of the anti-glare layer is preferably 10 μm or less, and more preferably 8 μm or less.

[0415] <Example of layer structure>

[0416] The following (1) to (5) are examples of the layer structure of the optical film of the present disclosure.

[0417] (1) A structure having a low refractive index layer on a biaxially stretched plastic film.

[0418] (2) A structure in which a hard coat layer and a low refractive index layer are sequentially provided on a biaxially stretched plastic film.

[0419] (3) A structure in which a high refractive index layer and a low refractive index layer are sequentially provided on a biaxially stretched plastic film.

[0420] (4) A structure in which an antiglare layer and a low refractive index layer are sequentially provided on a biaxially stretched plastic film.

[0421] (5) A structure in which a hard coating layer, a high refractive index layer and a low refractive index layer are sequentially provided on a biaxially stretched plastic film.

[0422] In order to maintain mechanical properties and suppress excessive deviation of optical properties such as in-plane phase difference to effectively suppress black screen, the overall thickness of the optical film is preferably 100 μm or less, more preferably 60 μm or less. In addition, in the optical film, the balance between the thickness of the biaxially stretched plastic film and the thickness of the layer other than the biaxially stretched plastic film is preferably 10:4 to 10:0.5.

[0423] <Shape, size>

[0424] The optical film may be in the form of a single sheet cut into a specified size, or in the form of a roll in which a long strip is wound into a roll. In addition, the size of a single sheet is not particularly limited, but the maximum diameter is about 2 inches or more and 500 inches or less, and in the present disclosure, it is preferably 30 inches or more and 80 inches or less. "Maximum diameter" refers to the maximum length when connecting any two points of the optical film. For example, when the optical film is rectangular, the diagonal of the rectangular area is the maximum diameter. In addition, when the optical film is circular, the diameter is the maximum diameter.

[0425] The width and length of the roll are not particularly limited. Generally speaking, the width is about 500 mm or more and 3000 mm or less, and the length is about 100 m or more and 5000 m or less. The roll-shaped optical film can be cut into a single piece for use according to the size of the image display device, etc. When cutting, it is preferred to remove the end of the roll with unstable physical properties.

[0426] In addition, the shape of a single sheet is not particularly limited, and can be, for example, a polygon (triangle, quadrilateral, pentagon, etc.), a circle, or a random amorphous shape. More specifically, when the optical film is a quadrilateral, the aspect ratio is not particularly limited as long as it does not cause problems as a display screen. For example, aspect ratios of 1:1, 4:3, 16:10, 16:9, 2:1, etc. can be cited.

[0427] <Purpose>

[0428] The optical film of the present disclosure can be suitably used as an optical film for an image display device.

[0429] The optical film of the present disclosure can be suitably used as an optical film disposed on the light emitting surface side of a display element of an image display device. In this case, it is preferable to provide a polarizer between the display element and the optical film of the present disclosure.

[0430] Furthermore, when the biaxially stretched plastic film satisfies condition 2, it is possible to suppress the following situations: the bending tendency remains or the breakage occurs after the bending test regardless of the bending direction. Therefore, when the biaxially stretched plastic film satisfies condition 2, it can be more suitably used as a plastic film for a curved image display device or a foldable image display device.

[0431] [Polarizing plate]

[0432] The polarizing plate of the present disclosure is a polarizing plate having a polarizer, a first transparent protective plate arranged on one side of the polarizer, and a second transparent protective plate arranged on the other side of the polarizer, wherein at least one of the first transparent protective plate and the second transparent protective plate is the above-mentioned optical film of the present disclosure.

[0433] In the polarizing plate, the optical film is preferably arranged so that the surface on the biaxially stretched plastic film side faces the polarizer side.

[0434] Figure 5 is a cross-sectional view showing an embodiment of a polarizing plate 700 of the present disclosure. Figure 5 The polarizing plate 700 includes a polarizer 300, a first transparent protective plate (500) disposed on one side of the polarizer, and a second transparent protective plate (600) disposed on the other side of the polarizer. Figure 5The polarizing plate 700 uses the optical film 100 as the first transparent protective plate (500). Figure 5 In the polarizing plate 700 , the polarizer 300 , the first transparent protective plate ( 500 ) and the second transparent protective plate ( 600 ) are stacked with the adhesive layer 400 interposed therebetween.

[0435] The polarizing plate is used to provide antireflection properties in combination with a λ / 4 phase difference plate, for example. In this case, the λ / 4 phase difference plate is disposed on the display element of the image display device, and the polarizing plate is disposed on the observer side of the λ / 4 phase difference plate.

[0436] In addition, when the polarizing plate is used for a liquid crystal display device, it is used to give the function of a liquid crystal shutter. In this case, in the liquid crystal display device, the lower polarizing plate, the liquid crystal display element, and the upper polarizing plate are arranged in this order, and the absorption axis of the polarizer of the lower polarizing plate is arranged perpendicular to the absorption axis of the polarizer of the upper polarizing plate. In the structure of the liquid crystal display device, the polarizing plate disclosed in the present invention is preferably used as the upper polarizing plate.

[0437] <Transparent protective plate>

[0438] The polarizing plate of the present disclosure uses the optical film of the present disclosure as at least one of the first transparent protective plate and the second transparent protective plate. It is preferred that both the first transparent protective plate and the second transparent protective plate are the optical film of the present disclosure.

[0439] In the case where one of the first transparent protective plate and the second transparent protective plate is the above-mentioned optical film of the present disclosure, the transparent protective plate of the other party is not particularly limited, but an optically isotropic transparent protective plate is preferred. In this specification, an optically isotropic transparent protective plate refers to a transparent protective plate having an in-plane phase difference of less than 20 nm, preferably less than 10 nm, and more preferably less than 5 nm. Regarding transparent protective plates with optical isotropy, acrylic films, cyclic polyolefin films, triacetyl cellulose (TAC) films, etc. can be listed. When the moisture permeability is similar to that of a biaxially stretched plastic film, the polarizing plate is not easily deformed after absorbing water, and can also protect the polarizer well, so acrylic films and cyclic polyolefin films are preferred.

[0440] Furthermore, when only one of the first transparent protective plate and the second transparent protective plate is the above-mentioned optical film of the present disclosure, it is preferable to use the above-mentioned optical film of the present disclosure as the transparent protective plate on the light emitting side.

[0441] <Polarizer>

[0442] Examples of polarizers include sheet-type polarizers (polyvinyl alcohol films, polyvinyl formal films, polyvinyl acetal films, ethylene-vinyl acetate copolymer saponified films, etc.) formed by stretching films dyed with iodine or the like, wire grid polarizers composed of a plurality of metal wires arranged in parallel, coating polarizers coated with lyotropic liquid crystal and dichroic guest-host materials, multilayer film polarizers, etc. Furthermore, these polarizers may be reflective polarizers having a function of reflecting non-transmitted polarized light components.

[0443] The polarizer is preferably arranged so that the angle between its absorption axis and the slow axis of the biaxially stretched plastic film is within 90 degrees ± 5 degrees, more preferably within 90 degrees ± 3 degrees, and even more preferably within 90 degrees ± 1 degree.

[0444] [Image display device (1)]

[0445] The image display device (1) disclosed in the present invention is an image display device having a display element and a polarizer and an optical film arranged on the light emitting surface side of the display element, wherein the optical film is the above-mentioned optical film disclosed in the present invention, and is arranged in a manner that the angle formed by the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film is within 90 degrees ± 5 degrees, and is arranged in a manner that the surface of the low refractive index layer side of the optical film faces the side opposite to the display element. The angle is preferably within 90 degrees ± 3 degrees, and more preferably within 90 degrees ± 1 degree.

[0446] Figure 6 This is a cross-sectional view showing an embodiment of an image display device (1) of the present disclosure and an image display device (2) described later.

[0447] Figure 6 The image display device 1000 has a light emitting surface side ( Figure 6 The upper side of the optical film 100 is provided. Figure 6 The image display devices 100 of the embodiment of the present invention all include a polarizer 300 between the display element 800 and the optical film 100 .

[0448] In addition, the image display device 1000 is not limited to Figure 6 For example, in Figure 6 In the embodiment, the components constituting the image display device 1000 are arranged at predetermined intervals, but the components are preferably laminated integrally via an adhesive layer, etc. The image display device may also include components (other optical films, etc.) not shown.

[0449] <Display Components>

[0450] As display elements, liquid crystal display elements, EL display elements (organic EL display elements, inorganic EL display elements), plasma display elements, etc. can be listed, and LED display elements such as mini LED and micro LED display elements, liquid crystal display elements or LED display elements using QDs can be listed.

[0451] When the display element of the display device is a liquid crystal display element, a backlight is required on the surface of the liquid crystal display element on the opposite side to the resin sheet.

[0452] Furthermore, the image display device may be an image display device having a touch panel function.

[0453] Examples of the touch panel include a resistive film type, an electrostatic capacitance type, an electromagnetic induction type, an infrared type, and an ultrasonic type.

[0454] Regarding the touch panel function, the function may be added to the display element as in a cell-type touch panel liquid crystal display element, or a touch panel may be mounted on the display element.

[0455] In addition, if the biaxially stretched plastic film satisfies condition 2, the optical film can suppress the following situations: the bending tendency remains or the breakage occurs after the bending test. Therefore, if the biaxially stretched plastic film satisfies condition 2, the image display device is preferably a curved image display device or a foldable image display device.

[0456] Furthermore, when the image display device is a curved image display device or a foldable image display device, the display element is preferably an organic EL display element.

[0457] <Other plastic films>

[0458] The image display device of the present disclosure may have other plastic films within a range not impairing the effects of the present disclosure.

[0459] As the other plastic film, a plastic film having optical isotropy is preferred.

[0460] [Image display device (2)]

[0461] The image display device disclosed in the present invention is an image display device having a polarizer and an optical film on a light emitting surface of a display element, wherein:

[0462] The image display device is configured in such a way that the angle formed by the absorption axis direction of the polarizer and the left-right direction or the up-down direction of the display element is within ±5 degrees.

[0463] The optical film is configured in such a way that the angle formed by the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film is within 90 degrees ± 5 degrees,

[0464] The optical film comprises a low refractive index layer on a biaxially stretched plastic film having an in-plane phase difference of less than 2500 nm, wherein the low refractive index layer is located on the outermost surface of the optical film and has a region where the difference between the maximum and minimum values ​​of ΔEab is less than 17.0.

[0465] Here, measurement 1A is performed on laminate 1A to calculate the L* value, a* value, and b* value of the L*a*b* colorimetric system. Measurement 2A is performed on laminate 2A to calculate the L* value, a* value, and b* value of the L*a*b* colorimetric system. Based on the results of measurement 1A and measurement 2A, ΔEab is calculated according to condition 1A.

[0466] <Measurement 1A>

[0467] A laminate 1A is prepared by laminating a polarizer and an optical film in this order on a display element, wherein in the laminate 1A, the optical film is arranged with the surface of the low refractive index layer facing the side opposite to the polarizer, and further, the polarizer is arranged with the angle formed by the absorption axis of the polarizer and the left-right direction or the up-down direction of the display element within ±5 degrees, and the angle formed by the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film within 90 degrees ±5 degrees.

[0468] The display element of the stacked body 1A is made to display white, and the transmitted light emitted from the low refractive index layer side of the stacked body 1A is measured 1 degree at a range of an elevation angle of 0 degrees to 80 degrees and an azimuth angle of 0 degrees to 359 degrees, and the L* value, a* value and b* value of the L*a*b* color system are calculated from the transmitted light at each angle. The measurement area of ​​the transmitted light is an arbitrary 1mm in the plane. 2 Above and 10mm 2 The following area.

[0469] <Measurement 2A>

[0470] A laminate 2A was prepared in which a polarizer was laminated on the same display element as that of the above-mentioned measurement 1A.

[0471] The display element of the stacked body 2A is made to display white, and the transmitted light emitted from the polarizer side of the stacked body 2A is measured 1 degree at a range of an elevation angle of 0 degree to 80 degrees and an azimuth angle of 0 degree to 359 degrees, and the L* value, a* value and b* value of the L*a*b* colorimetric system are calculated from the transmitted light at each angle. The measurement area of ​​the transmitted light is substantially consistent with that of the measurement 1A in the plane.

[0472] <Condition 1A>

[0473] At all elevation angles and all azimuth angles, ΔL* is calculated by subtracting the L* value of measurement 2A from the L* value of measurement 1A, and all values ​​of ΔL* from the maximum value to the minimum value are grayscaled with a specified tone and displayed in grayscale in a two-dimensional coordinate system in which concentric circles represent the elevation angle and vertical and horizontal lines represent the azimuth angle.

[0474] It was confirmed that there were two regions where ΔL* was distributed in concentric circles in the two-dimensional coordinates, and that the two regions were located at substantially symmetrical positions in the two-dimensional coordinates.

[0475] Regarding the elevation angles at the center of the region where ΔL* is distributed in concentric circles, one elevation angle is α degrees and the other elevation angle is β degrees.

[0476] ΔEab at each azimuth angle is calculated based on the difference between the L* value, a* value, and b* value of measurement 1A when the azimuth angle is greater than 0 degrees and less than 359 degrees when the elevation angle is (α+β) / 2 and the L* value, a* value, and b* value of measurement 2A when the azimuth angle is greater than 0 degrees and less than 359 degrees when the elevation angle is (α+β) / 2.

[0477] The "laminated body 1A" in the measurement 1A of the image display device (2) refers to the image display device (2). In addition, the "laminated body 2" in the measurement 1B of the image display device (2) refers to the laminated body obtained by removing the optical film of the present disclosure described above from the image display device (2).

[0478] Measurement 1A and Measurement 2A in the image display device (2) of the present disclosure are the same as the above-mentioned Measurement 1 and Measurement 2 of the optical film of the present disclosure except that the surface light source and the display element are different.

[0479] In addition, the preferred embodiments of measurement 1A and measurement 2A are the same as the preferred embodiments of measurement 1 and measurement 2 (for example, the preferred ranges of L* value, a* value, and b* value in the state of laminate 2A are the same as the preferred ranges of L* value, a* value, and b* value in the state of laminate 2). In addition, the preferred embodiment of condition 1A is the same as the preferred embodiment of condition 1 described above.

[0480] [Method for selecting optical film for image display device]

[0481] Regarding the method for selecting an optical film for an image display device disclosed in the present invention, the image display device is formed by having a polarizer and an optical film on a light emitting surface of a display element, and is configured in a manner such that the direction of the absorption axis of the polarizer is parallel to the left-right direction or the up-down direction of the display element, wherein an optical film X having a low refractive index layer on a biaxially stretched plastic film having an in-plane phase difference of less than 2500nm, wherein the low refractive index layer is located on the outermost surface of the optical film X, and has a region where the difference between the maximum and minimum values ​​of ΔEab is less than 17.0 is used as a judgment condition, and an optical film X that satisfies the judgment condition is selected as the optical film.

[0482] Here, measurement 1B is performed on laminate 1B to calculate the L* value, a* value, and b* value of the L*a*b* colorimetric system, and measurement 2B is performed on laminate 2B to calculate the L* value, a* value, and b* value of the L*a*b* colorimetric system, and ΔEab is calculated based on the results of measurement 1B and measurement 2B according to condition 1B.

[0483] <Measurement 1B>

[0484] A laminate 1B is prepared by laminating a polarizer and the optical film X in this order on a display element, wherein in the laminate 1B, the optical film is arranged with the surface of the low refractive index layer facing the side opposite to the polarizer, and further, the polarizer is arranged with the angle formed by the absorption axis of the polarizer and the left-right direction or the up-down direction of the display element within ±5 degrees, and the angle formed by the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film X within 90 degrees ±5 degrees.

[0485] The display element of the stacked body 1B was made to display white, and the transmitted light emitted from the low refractive index layer side of the stacked body 1B was measured 1 degree at a range of an elevation angle of 0 degree to 80 degrees and an azimuth angle of 0 degree to 359 degrees, and the L* value, a* value and b* value of the L*a*b* color system were calculated from the transmitted light at each angle. The measurement area of ​​the transmitted light was an arbitrary 1 mm2 area within the surface. 2 Above and 10mm 2 The following area.

[0486] <Measurement 2B>

[0487] A laminate 2B was prepared in which a polarizer was laminated on the same display element as in the above-mentioned measurement 1B.

[0488] The display element of the stacked body 2B is made to display white, and the transmitted light emitted from the polarizer side of the stacked body 2B is measured 1 degree at a range of an elevation angle of not less than 0 degree and not more than 80 degrees and an azimuth angle of not less than 0 degree and not more than 359 degrees. The L* value, a* value and b* value of the L*a*b* colorimetric system are calculated based on the transmitted light at each angle, and the measurement area of ​​the transmitted light is roughly consistent with that of measurement 1B within the plane.

[0489] <Condition 1B>

[0490] At all elevation angles and all azimuth angles, ΔL* is calculated by subtracting the L* value measured in 2B from the L* value measured in 1B, and all values ​​of ΔL* from the maximum value to the minimum value are grayscaled in a specified tone and displayed in grayscale in a two-dimensional coordinate system in which concentric circles represent the elevation angle and vertical and horizontal lines represent the azimuth angle.

[0491] It was confirmed that there were two regions where ΔL* was distributed in concentric circles in the two-dimensional coordinates, and that the two regions were located at substantially symmetrical positions in the two-dimensional coordinates.

[0492] Regarding the elevation angles at the center of the region where ΔL* is distributed in concentric circles, one elevation angle is α degrees and the other elevation angle is β degrees.

[0493] ΔEab at each azimuth angle is calculated based on the difference between the L* value, a* value, and b* value of measurement 1B when the azimuth angle is greater than 0 degrees and less than 359 degrees when the elevation angle is (α+β) / 2, and the L* value, a* value, and b* value of measurement 2B when the azimuth angle is greater than 0 degrees and less than 359 degrees when the elevation angle is (α+β) / 2.

[0494] In the method for selecting an optical film for an image display device disclosed in the present invention, "an image display device configured in such a manner that the direction of the absorption axis of the polarizer is parallel to the left-right direction or the up-down direction of the display element" means that the angle formed by the direction of the absorption axis of the polarizer and the left-right direction or the up-down direction of the display element is within ±5 degrees. In addition, the angle formed is preferably within ±3 degrees, and more preferably within ±5 degrees.

[0495] Measurement 1B and Measurement 2B in the method for selecting an optical film for an image display device of the present disclosure are the same as the above-mentioned Measurement 1 and Measurement 2 of the optical film of the present disclosure except that the surface light source and the display element are different.

[0496] In addition, the preferred embodiments of measurement 1B and measurement 2B are the same as the preferred embodiments of measurement 1 and measurement 2 (for example, the preferred ranges of L* value, a* value and b* value in the state of laminate 2B are the same as the preferred ranges of L* value, a* value and b* value in the state of laminate 2). In addition, the preferred embodiment of condition 1B is the same as the preferred embodiment of condition 1 described above.

[0497] The method for selecting an optical film for an image display device of the present disclosure preferably further comprises an additional determination condition as a determination condition. As the additional determination condition, preferred embodiments of the optical film of the present disclosure (for example, a phase difference in the thickness direction, surface roughness, etc.) can be cited.

[0498] The method for selecting an optical film for an image display device disclosed in the present invention is useful as a method for selecting an optical film for an image display device having a polarizer on a surface on the light emitting surface side of a display element, and is particularly useful as a method for selecting an optical film for an image display device arranged in a manner such that the direction of the absorption axis of the polarizer is parallel to the left-right direction or the up-down direction of the display element.

[0499] Example

[0500] Next, the present disclosure will be described in more detail by way of examples, but the present disclosure is not limited to these examples at all.

[0501] 1. Measurement and evaluation

[0502] The following measurement and evaluation were performed under an atmosphere of 23° C.±5° C. and a relative humidity of 40% RH or more and 65% RH or less. In addition, the sample was exposed to the atmosphere for 30 minutes or more before the measurement and evaluation.

[0503] 1-1. In-plane phase difference (Re), phase difference in thickness direction (Rth), and direction of slow axis

[0504] Samples measuring 50 mm in length and 50 mm in width were cut out from the plastic films prepared or made by the following "2" and used in the examples, comparative examples, and reference examples. At this time, the conveying direction (MD direction) of the plastic film was regarded as the longitudinal direction, and the width direction (TD direction) of the plastic film was regarded as the transverse direction. For four parts advancing 10 mm from the four corners of the sample toward the central part and the central part of the sample, a total of five parts, the in-plane phase difference, the phase difference in the thickness direction, and the direction of the slow axis were measured. The averages of Re1 to Re5 calculated from the measurement results are shown in Table 1. The measuring device used was a device named "RETS-100 (measurement point: diameter 5 mm)" manufactured by Otsuka Electronics Co., Ltd. And for the direction of the slow axis, measurements were made in the range of 0 degrees or more and 90 degrees or less with 0 degrees based on the conveying direction (MD direction) of the plastic film.

[0505] 1-2. Flexural resistance

[0506]

[0507] A long strip-shaped sample measuring 30 mm in the short side (TD direction) and 100 mm in the long side (MD direction) was cut out from the plastic film prepared or made by the following "2" and used in the examples, comparative examples, and reference examples. The two ends of the short side (30 mm) of the sample were fixed (the area 10 mm from the end was fixed) to a durability testing machine (product name "DLDMLH-FS", YUASA SYSTEM CO., LTD.), and a continuous folding test of folding 180 degrees 100,000 times was carried out. The folding speed was 120 times per minute. The more detailed method of the folding test is shown below.

[0508] After the folding test, the long strip-shaped sample was placed on a horizontal table, and the angle at which the end of the sample翘起 from the table was measured. If the angle was 15 degrees or less, it was at a qualified level. The results are shown in Table 1. And the case where the sample broke midway was regarded as "broken".

[0509] <MD direction>

[0510] A long strip-shaped sample measuring 30 mm in the short side (MD direction) and 100 mm in the long side (TD direction) was cut out from the plastic film prepared or made by the following "2" and used in the examples, comparative examples, and reference examples, and the same evaluation as above was carried out.

[0511] <Details of the folding test>

[0512] As Fig.10As shown in (A) of FIG. 1 , in the continuous folding test, first, the side portion 10C of the plastic film 10 and the side portion 10D facing the side portion 10C are fixed by the fixing portions 60 arranged in parallel. The fixing portions 60 can slide in the horizontal direction.

[0513] Then, if Fig.10 As shown in (B), by moving the fixing parts 60 in a manner close to each other, the plastic film 10 is deformed in a folded manner, and then, as shown in FIG. Fig.10 As shown in (C), the fixing part 60 is moved until the interval between two opposing sides of the plastic film 10 fixed by the fixing part 60 becomes 2 mm, and then the fixing part 60 is moved in the reverse direction to eliminate the deformation of the plastic film 10.

[0514] like Fig.10 As shown in (A) to (C), the plastic film 10 can be folded 180 degrees by moving the fixing portion 60. In addition, the continuous folding test is performed in a manner that the curved portion 10E of the plastic film 10 does not protrude from the lower end of the fixing portion 60, and the interval when the fixing portions 60 are closest is controlled to 2 mm, thereby making it possible to make the interval between the two opposing sides of the optical film 10 2 mm.

[0515] 1-3. Calculation of the difference between the maximum and minimum values ​​of ΔEab

[0516] A liquid crystal display device having a polarizer on a liquid crystal display element was prepared (trade name of EIZO company "EV2450"; horizontal: 527.0 mm, vertical: 596.4 mm; the absorption axis of the polarizer is parallel to the vertical direction of the screen; backlight: backlight using a white light emitting diode). The liquid crystal display device is regarded as a laminate 2. The liquid crystal display device (laminate 2) was made to display white in a dark room environment, and measurement 2 of this specification was performed at various angles using a device of ELDIM company's trade name "EzContrast". The measurement area is a circle with a diameter of 2 mm (area of ​​approximately 3.14 mm 2 ).

[0517] Next, a laminate 1 was prepared in which the optical films of the embodiment and the comparative example were arranged on the above-mentioned liquid crystal display device via an adhesive layer. At this time, the absorption axis of the polarizer and the slow axis of the plastic film of the optical film were arranged at 90 degrees. Then, the laminate 1 was made to display white in a dark room environment, and the measurement 1 of this specification was performed at various angles using a device named "EzContrast" of ELDIM. The measurement area is a circle with a diameter of 2 mm (an area of ​​about 3.14 mm 2 , which is consistent with the area of ​​measurement 1).

[0518] Measurements 1 and 2 were performed at the center positions within the planes of the laminate 1 and the laminate 2 .

[0519] Next, based on steps (3-1) to (3-4) in the main text of the specification, ΔEab at each azimuth angle is calculated, and then the difference between the maximum and minimum values ​​of ΔEab is calculated. In addition, steps (3-1) to (3-4) are performed using a device called "EzContrast" and its accompanying software "EzCom" from ELDIM (the grayscale of (3-1) above is 16 levels of grayscale). The results are shown in Table 1.

[0520] In addition, in the state of laminated body 2, the average of L* value, a* value and b* value, and the deviation (3σ) of L* value, a* value and b* value represent the following values. In other words, in measurement 2, the average of L* value, a* value and b* value, and the deviation (3σ) of L* value, a* value and b* value are parameters representing the following values.

[0521] Average L* value at all angles: 95.9

[0522] Average a* value of all angles: 4.2

[0523] Average b* value of all angles: -4.6

[0524] Deviation of L* value at all angles (3σ): 113.3

[0525] Deviation of a* value at all angles (3σ): 10.7

[0526] Deviation of b* value at all angles (3σ): 14.1

[0527] 1-4. Evaluation of uneven rainbow

[0528] The laminate 1 is prepared in the same manner as 1-3 above. At this time, the slow axis of the biaxially stretched plastic film of the optical film is arranged perpendicular to the absorption axis of the polarizer of the polarizing plate. A surface light source (liquid crystal display element) is used to display white in a dark room environment, and the face is moved up and down, left and right at a distance of more than 30 cm and less than 100 cm from the laminate 1, and observed from the directions of ±90 degrees up and down and ±90 degrees left and right. The evaluator is a healthy person of about 20 years old with a visual acuity of more than 0.7, and the presence or absence of rainbow unevenness is evaluated with the naked eye according to the following criteria. The visual acuity also includes corrected visual acuity.

[0529] A: Rainbow unevenness is not observable at all locations and when viewed from all directions.

[0530] B: Rainbow unevenness exists slightly in a position and / or direction observed in a very small area.

[0531] C: Rainbow unevenness exists in a large number of positions and / or directions observed in a very small area.

[0532] D: Rainbow unevenness exists in a large amount in positions and / or directions observed in most areas.

[0533] 1-5. Evaluation of color distortion

[0534] The laminate 1 is prepared in the same manner as 1-3 above. At this time, the slow axis of the biaxially stretched plastic film of the optical film is arranged perpendicular to the absorption axis of the polarizer of the polarizing plate. In a dark room environment, a surface light source (liquid crystal display element) is made to display white, and the elevation angle is fixed to about (α+β) / 2. In this state, the surroundings of the laminate 1 are observed for one week. The observation can be said to be an observation with an azimuth angle of 0 to 359 degrees performed in a state where the elevation angle is fixed to about (α+β) / 2. The observation is carried out at a distance of more than 30 cm and less than 100 cm from the laminate 1. The evaluator is a healthy person of about 20 years old with a visual acuity of more than 0.7, and the presence or absence of color distortion is evaluated with the naked eye according to the following criteria. The visual acuity also includes corrected visual acuity.

[0535] A: Colors are viewed the same way at all angles.

[0536] B: There are a small number of azimuths where the colors appear different.

[0537] C: There are many angles where the colors appear different.

[0538] D: The colors appear different at most azimuths.

[0539] 1-6. Measurement of reflectivity

[0540] The following sample (5 cm × 5 cm) was prepared: a black plate (KURARAY CO., LTD., product name "COMOGLASDFA2CG 502K (Black) type", total light transmittance of 0%, thickness of 2 mm, refractive index of 1.49) was adhered to the biaxially stretched plastic film side of the optical film of the embodiment and the comparative example via a 25 μm thick transparent adhesive layer (PANAC CO., LTD., product name "Panaclean PD-S1", refractive index of 1.49).

[0541] When the direction perpendicular to the surface of the low refractive index layer side of the sample is set to 0 degrees, light is incident on the sample from a direction of 5 degrees, and the reflectivity (visual reflectivity Y value) is measured based on the regular reflection light of the incident light. Regarding the reflectivity, a spectroscopic reflectivity measuring instrument (SHIMADZU CORPORATION, trade name: MPC3100) is used to measure the 5° regular reflectivity within a wavelength range of more than 380nm and less than 780nm, and then, the software (MPC3100 built-in. Conditions for calculating the reflectivity: C light source; viewing angle of 2 degrees) converted to the brightness felt by the human eye is calculated, and the value representing the visual reflectivity is used as the reflectivity. The reflectivity at 10 locations is measured for each sample, and the average value is used as the reflectivity of each sample.

[0542] 2. Preparation and production of biaxially stretched polyester film

[0543] [Biaxially stretched polyester film 1]

[0544] 1 kg of PET (melting point: 258°C, absorption center wavelength: 320 nm) and 0.1 kg of ultraviolet absorber (2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazinone-4-one) were melt-mixed at 280°C in a kneader to prepare pellets containing the ultraviolet absorber. The pellets and PET having a melting point of 258°C were put into a single screw extruder and melt-mixed at 280°C, extruded from a T-die, and cast on a casting drum whose surface temperature was controlled to 25°C to obtain a cast film. The amount of the ultraviolet absorber in the cast film was 1 part by mass relative to 100 parts by mass of PET.

[0545] After the obtained cast film was heated by a roller set at 95°C, the film was stretched 3.3 times in the conveying direction while heating both the front and back sides of the film by a radiation heater so that the film temperature at a point of 250 mm in a 400 mm stretching section (starting point is stretching roller A, end point is stretching roller B, and stretching rollers A and B each have two press rollers) was 103°C, and then temporarily cooled. In addition, when heating by the radiation heater, a wind of 92°C and 4 m / s was blown to the film from the side of the radiation heater opposite to the film, thereby generating turbulence on the front and back sides of the film, and disturbing the temperature uniformity of the film.

[0546] Next, both surfaces of the uniaxially stretched film were subjected to corona discharge treatment in air so that the wetting tension of the base film was 55 mN / m, and a "lubricating layer coating liquid comprising a polyester resin having a glass transition temperature of 18°C, a polyester resin having a glass transition temperature of 82°C, and silica particles having an average particle size of 100 nm" was applied online to the corona discharge treated surfaces of both surfaces of the film to form an lubricating layer.

[0547] Next, the uniaxially stretched film was introduced into a tenter, and after being preheated with hot air at 95°C, it was stretched 4.5 times in the width direction of the film at a temperature of 105°C in the first stage and 140°C in the second stage. Here, when the transverse stretching section was divided into two equal parts, the film was stretched in two stages so that the stretching amount of the film at the middle point of the transverse stretching section (film width at the measuring point - film width before stretching) became 80% of the stretching amount at the end of the transverse stretching section. The film after transverse stretching was heat-treated in stages in the tenter with hot air from 180°C to 245°C, which is a heat treatment temperature, and then a 1% relaxation treatment was performed in the width direction under the same temperature conditions. After further rapid cooling to 100°C, a 1% relaxation treatment was performed in the width direction, and then it was wound up to obtain a biaxially stretched polyester film 1 (the biaxially stretched polyester film used in Example 1) with a thickness of 40 μm.

[0548] [Biaxially stretched polyester film 2]

[0549] As the biaxially stretched polyester film used in Comparative Example 1, a commercially available biaxially stretched polyester film (TOYOBO CO., LTD., trade name: Cosmoshine A4100, thickness: 50 μm) was prepared.

[0550] [Biaxially stretched polyester film 3]

[0551] A biaxially stretched polyester film 3 (the biaxially stretched polyester film used in Example 2) having a thickness of 40 μm was obtained in the same manner as the biaxially stretched polyester film 1 except that the stretching ratio in the width direction was changed from 4.5 times to 5.1 times.

[0552] [Biaxially stretched polyester film 4]

[0553] A biaxially stretched polyester film 4 (a biaxially stretched polyester film used in Example 3) was obtained in the same manner as the biaxially stretched polyester film 3 except that the thickness of the cast film of the biaxially stretched polyester film 1 was increased to change the final thickness to 80 μm.

[0554] [Biaxially stretched polyester film 5]

[0555] As the biaxially stretched polyester film used in Comparative Example 2, a commercially available biaxially stretched polyester film (Toray Industries, Inc., trade name: 75U403, thickness: 75 μm) was prepared.

[0556] [Biaxially stretched polyester film 6]

[0557] As the biaxially stretched polyester film used in Comparative Example 3, a commercially available biaxially stretched polyester film (TOYOBO CO., LTD., trade name: Cosmoshine A4300, thickness: 23 μm) was prepared.

[0558] 3. Production of optical films

[0559] The hard coat layer-forming coating liquid of the following formulation was applied to the biaxially stretched polyester film 1 prepared in the above step 2, and then dried at 70° C. for 1 minute to volatilize the solvent. Then, ultraviolet irradiation (100 mJ / cm 2 ) to form a hard coating layer (dry thickness: 10 μm).

[0560] The coating liquid 1 for forming a low refractive index layer having the following formulation was applied on the hard coat layer, and then dried at 60° C. for 1 minute to volatilize the solvent. Then, ultraviolet irradiation (200 mJ / cm 2 ) to form a low refractive index layer (dry thickness is 100nm) to obtain the optical film of Example 1.

[0561] <Hard Coat Layer Forming Coating Liquid>

[0562] Composition containing ultraviolet curable acrylate: 22 parts by mass

[0563] (Nippon Kayaku Co., Ltd., trade name "KAYARAD PET-30", solid content: 100%)

[0564] Composition containing ultraviolet curable acrylate: 17 parts by mass

[0565] (DKS Co. Ltd., trade name: NewFrontier R-1403M, solid content: 80%)

[0566] Fluorine leveling agent: 1 part by mass

[0567] (DIC Corporation, trade name "MEGAFACEF F-568")

[0568] Photopolymerization initiator: 1 part by mass

[0569] (IGM Resins BV, trade name "Omnirad 184")

[0570] Methyl isobutyl ketone: 15 parts by mass

[0571] Methyl ethyl ketone: 44 parts by mass

[0572] <Coating liquid for forming low refractive index layer>

[0573] Composition containing ultraviolet curable acrylate: 1 part by mass

[0574] (Nippon Kayaku Co., Ltd., trade name "KAYARAD PET-30", solid content: 100%)

[0575] Photopolymerization initiator: 0.2 parts by mass

[0576] (IGM Resins BV, trade name "Omnirad 127")

[0577] Hollow silica particles: 1.3 parts by mass

[0578] (Average primary particle size 60nm)

[0579] Solid silica particles: 0.7 parts by mass

[0580] (Average primary particle size 15nm)

[0581] Leveling agent: 0.1 parts by mass

[0582] (Dainichiseika Color & Chemicals Mfg. Co., Ltd., trade name: SEIKABEAM 10-28 (MB))

[0583] Dilution solvent: 90 parts by mass

[0584] (MIBK / AN=7 / 3)

[0585] [Examples 2-3]

[0586] Optical films of Examples 2 and 3 were obtained in the same manner as in Example 1 except that the biaxially stretched polyester film 1 was changed to the biaxially stretched polyester films 3 and 4 prepared in the above “2”.

[0587] [Comparative Example 1]

[0588] An optical film of Comparative Example 1 was obtained in the same manner as in Example 1 except that the biaxially stretched polyester film 1 was changed to the biaxially stretched polyester film 2 prepared in the above “2”.

[0589] [Comparative Examples 2 to 3]

[0590] Optical films of Comparative Examples 2 and 3 were obtained in the same manner as in Example 1 except that the biaxially stretched polyester film 1 was changed to the biaxially stretched polyester films 5 and 6 prepared in the above “2”.

[0591] [Reference Example 1]

[0592] The biaxially stretched polyester film 3 alone (a form in which a hard coat layer and a low refractive index layer are not formed on the biaxially stretched polyester film 3 ) is used as the optical film of Reference Example 1.

[0593] [Reference Example 2]

[0594] The optical film of Reference Example 2 was made of a single body of the biaxially stretched polyester film 2 (a form in which a hard coat layer and a low refractive index layer were not formed on the biaxially stretched polyester film 2 ).

[0595] [Reference Example 3]

[0596] As the optical film of Reference Example 3, a commercially available uniaxially stretched polyester film (Toyobo Co., Ltd., trade name: Cosmoshine TA048, thickness: 80 μm) was used alone.

[0597] [Table 1]

[0598]

[0599] From the results in Table 1, it can be confirmed that the optical film of the embodiment in which the difference between the maximum and minimum values ​​of ΔEab is less than 17.0 can suppress rainbow unevenness when observed with the naked eye without increasing the in-plane phase difference. Furthermore, from the results in Table 1, it can be confirmed that the optical film of the embodiment in which the difference between the maximum and minimum values ​​of ΔEab is less than 17.0 can suppress color distortion. In contrast, it can be confirmed that although the optical film of the comparative example has a low refractive index layer and has the same reflectivity as the optical film of the embodiment, it cannot suppress rainbow unevenness and color distortion.

[0600] In addition, it can be confirmed that regardless of the bending direction, the optical film of the embodiment can suppress the situation where the bending tendency remains or the breakage occurs after the bending test (regarding the optical film of the embodiment, compared with the uniaxially stretched polyester film (Reference Example 3) and the general biaxially stretched film (Comparison Examples 1 to 3), the bending tendency is unlikely to remain and no breakage will occur).

[0601] Furthermore, although the ΔEab in Table 1 is a value based on the measurement results at the center position within the surface of the stack 1 and the stack 2, the same result is obtained even if the measurement position is offset (for example, the ΔEab at a position 130 mm to the left of the center position (other measurement position 1), a position 130 mm to the right of the center position (other measurement position 2), a position 75 mm above the center position (other measurement position 3), and a position 75 mm below the center position (other measurement position 4) are approximately the same as the values ​​in Table 1).

Claims

1. An optical film having a low refractive index layer on a plastic film, wherein: The plastic film is a biaxially stretched plastic film with an in-plane phase difference of less than 2500 nm. The low refractive index layer is located on the outermost surface of the optical film. The optical film has a lower region where the difference between the maximum and minimum values ​​of ΔEab is less than 17.0, Here, measurement 1 is performed on laminate 1 to calculate the L* value, a* value, and b* value of the L*a*b* colorimetric system, and measurement 2 is performed on laminate 2 to calculate the L* value, a* value, and b* value of the L*a*b* colorimetric system. Based on the results of measurement 1 and measurement 2, ΔEab is calculated according to condition 1. <Measurement 1> A laminate 1 is prepared by laminating a polarizer and the optical film in this order on a surface light source, wherein in the laminate 1, the optical film is arranged in such a manner that the surface of the low refractive index layer side faces the side opposite to the polarizer, and further, the polarizer is arranged in such a manner that the angle formed by the absorption axis of the polarizer and the left-right direction or the up-down direction of the surface light source is within ±5 degrees, and the angle formed by the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film is within 90 degrees ±5 degrees, The surface light source of the stacked body 1 is made to display white, and the transmitted light emitted from the low refractive index layer side of the stacked body 1 is measured 1 degree at a range of an elevation angle of 0 degrees to 80 degrees and an azimuth angle of 0 degrees to 359 degrees. The L* value, a* value and b* value of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area of ​​the transmitted light is any 1mm in the plane. 2 Above and 10mm 2 The following areas; <Measurement 2> A laminate 2 is prepared by laminating a polarizer on the same surface light source as that in the measurement 1, and the absorption axis of the polarizer is arranged in the same direction as that in the measurement 1 relative to the surface light source. The surface light source of the stacked body 2 is made to display white, and the transmitted light emitted from the polarizer side of the stacked body 2 is measured 1 degree at a range of an elevation angle of not less than 0 degree and not more than 80 degrees and an azimuth angle of not less than 0 degree and not more than 359 degrees, and the L* value, a* value and b* value of the L*a*b* colorimetric system are calculated based on the transmitted light at each angle, and the measurement area of ​​the transmitted light is substantially consistent with that of measurement 1 within the plane; <Condition 1> At all elevation angles and all azimuth angles, ΔL* is calculated by subtracting the L* value of measurement 2 from the L* value of measurement 1, and all values ​​of ΔL* from the maximum value to the minimum value are grayscaled with a specified color tone and displayed in grayscale in a two-dimensional coordinate system in which concentric circles represent elevation angles and vertical and horizontal circles represent azimuth angles. It was confirmed that there were two regions where ΔL* was distributed in concentric circles in the two-dimensional coordinates, and that the two regions were located at approximately symmetrical positions in the two-dimensional coordinates. Regarding the elevation angle at the center of the region where ΔL* is distributed in concentric circles, let one elevation angle be α degrees and the other elevation angle be β degrees. ΔEab at each azimuth angle is calculated based on the difference between the L* value, a* value, and b* value of measurement 1 when the azimuth angle is greater than 0 degrees and less than 359 degrees when the elevation angle is (α+β) / 2, and the L* value, a* value, and b* value of measurement 2 when the azimuth angle is greater than 0 degrees and less than 359 degrees when the elevation angle is (α+β) / 2.

2. The optical film according to claim 1, wherein The plastic film is a biaxially stretched plastic film having an in-plane phase difference of 0.10 or less relative to a phase difference in a thickness direction.

3. The optical film according to claim 1 or 2, wherein: One or more layers selected from a hard coat layer, an antiglare layer, and a high refractive index layer are provided between the plastic film and the low refractive index layer.

4. The optical film according to any one of claims 1 to 3, wherein The plastic film has a thickness of 15 μm or more and 200 μm or less.

5. A polarizing plate comprising: a polarizer; a first transparent protective plate disposed on one side of the polarizer; and a second transparent protective plate disposed on the other side of the polarizer, wherein: At least one of the first transparent protective plate and the second transparent protective plate is the optical film according to any one of claims 1 to 4.

6. An image display device comprising a display element and a polarizer and an optical film arranged on the light emitting surface side of the display element, wherein: The optical film is an optical film as described in any one of claims 1 to 4, and is configured in a manner that the angle formed by the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film is within 90 degrees ± 5 degrees, and is configured in a manner that the surface of the low refractive index layer side of the optical film faces the side opposite to the display element.

7. An image display device comprising a polarizer and an optical film on a light emitting surface of a display element, wherein: The image display device is configured in such a way that the angle formed by the absorption axis direction of the polarizer and the left-right direction or the up-down direction of the display element is within ±5 degrees. The optical film is configured in such a way that the angle formed by the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film is within 90 degrees ± 5 degrees, The optical film is formed by having a low refractive index layer on a biaxially stretched plastic film having an in-plane phase difference of less than 2500 nm, wherein the low refractive index layer is located on the outermost surface of the optical film and has a region where the difference between the maximum and minimum values ​​of ΔEab is less than 17.0, Here, measurement 1A is performed on laminate 1A to calculate the L* value, a* value, and b* value of the L*a*b* colorimetric system. Measurement 2A is performed on laminate 2A to calculate the L* value, a* value, and b* value of the L*a*b* colorimetric system. Based on the results of measurement 1A and measurement 2A, ΔEab is calculated according to condition 1A. <Measurement 1A> A laminate 1A is prepared by laminating a polarizer and the optical film in this order on a display element, wherein in the laminate 1A, the optical film is arranged in such a manner that the surface on the low refractive index layer side faces the side opposite to the polarizer, and further, the polarizer is arranged in such a manner that the angle formed by the absorption axis of the polarizer and the left-right direction or the up-down direction of the display element is within ±5 degrees, and the angle formed by the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film is within 90 degrees ±5 degrees, The display element of the stacked body 1A is made to display white, and the transmitted light emitted from the low refractive index layer side of the stacked body 1A is measured 1 degree at a range of an elevation angle of 0 degree to 80 degrees and an azimuth angle of 0 degree to 359 degrees, and the L* value, a* value and b* value of the L*a*b* colorimetric system are calculated from the transmitted light at each angle, and the measurement area of ​​the transmitted light is an arbitrary 1mm in the plane. 2 Above and 10mm 2 The following areas; <Measurement 2A> A laminate 2A is prepared by laminating a polarizing element on the same display element as that of the measurement 1A. The display element of the stacked body 2A is made to display white, and the transmitted light emitted from the polarizer side of the stacked body 2A is measured 1 degree at a range of an elevation angle of not less than 0 degree and not more than 80 degrees and an azimuth angle of not less than 0 degree and not more than 359 degrees, and the L* value, a* value and b* value of the L*a*b* colorimetric system are calculated based on the transmitted light at each angle, and the measurement area of ​​the transmitted light is substantially consistent with that of the measurement 1A in the plane; <Condition 1A> At all elevation angles and all azimuth angles, ΔL* is calculated by subtracting the L* value of measurement 2A from the L* value of measurement 1A, and all values ​​of ΔL* from the maximum value to the minimum value are grayscaled with a specified color tone and displayed in grayscale in a two-dimensional coordinate system in which concentric circles represent elevation angles and vertical and horizontal circles represent azimuth angles. It was confirmed that there were two regions where ΔL* was distributed in concentric circles in the two-dimensional coordinates, and that the two regions were located at approximately symmetrical positions in the two-dimensional coordinates. Regarding the elevation angle at the center of the region where ΔL* is distributed in concentric circles, let one elevation angle be α degrees and the other elevation angle be β degrees. ΔEab at each azimuth angle is calculated based on the difference between the L* value, a* value, and b* value of measurement 1A when the azimuth angle is greater than 0 degrees and less than 359 degrees when the elevation angle is (α+β) / 2 and the L* value, a* value, and b* value of measurement 2A when the azimuth angle is greater than 0 degrees and less than 359 degrees when the elevation angle is (α+β) / 2.

8. A method for selecting an optical film for an image display device, wherein the image display device comprises a polarizer and an optical film on a light emitting surface of a display element, and the polarizer is arranged in such a way that the absorption axis direction is parallel to the left-right direction or the up-down direction of the display element, wherein: The optical film X is formed by having a low refractive index layer on a biaxially stretched plastic film having an in-plane phase difference of less than 2500 nm, the low refractive index layer is located on the outermost surface of the optical film X, and has a region where the difference between the maximum value and the minimum value of ΔEab is less than 17.0 as a judgment condition, and the optical film X that satisfies the judgment condition is selected as the optical film, Here, measurement 1B is performed on laminate 1B to calculate the L* value, a* value, and b* value of the L*a*b* colorimetric system. Measurement 2B is performed on laminate 2B to calculate the L* value, a* value, and b* value of the L*a*b* colorimetric system. Based on the results of measurement 1B and measurement 2B, ΔEab is calculated according to condition 1B. <Measurement 1B> A laminate 1B is prepared in which a polarizer and the optical film X are laminated in this order on a display element, wherein in the laminate 1B, the optical film is arranged in such a manner that the surface of the low refractive index layer side faces the side opposite to the polarizer, and further, the polarizer is arranged in such a manner that the angle formed by the absorption axis of the polarizer and the left-right direction or the up-down direction of the display element is within ±5 degrees, and the angle formed by the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film X is within 90 degrees ±5 degrees, The display element of the stacked body 1B was made to display white, and the transmitted light emitted from the low refractive index layer side of the stacked body 1B was measured 1 degree at a range of an elevation angle of 0 degree to 80 degrees and an azimuth angle of 0 degree to 359 degrees, and the L* value, a* value and b* value of the L*a*b* color system were calculated from the transmitted light at each angle. The measurement area of ​​the transmitted light was an arbitrary 1 mm2 area within the surface. 2 Above and 10mm 2 The following areas; <Measurement 2B> A laminate 2B is prepared in which a polarizer is laminated on the same display element as that of the measurement 1B. The display element of the stacked body 2B is made to display white, and the transmitted light emitted from the polarizer side of the stacked body 2B is measured 1 degree at a range of an elevation angle of not less than 0 degree and not more than 80 degrees and an azimuth angle of not less than 0 degree and not more than 359 degrees, and the L* value, a* value and b* value of the L*a*b* colorimetric system are calculated based on the transmitted light at each angle, and the measurement area of ​​the transmitted light is substantially consistent with that of the measurement 1B in the plane; <Condition 1B> At all elevation angles and all azimuth angles, ΔL* is calculated by subtracting the L* value of measurement 2B from the L* value of measurement 1B, and all values ​​of ΔL* from the maximum value to the minimum value are grayscaled with a specified color tone and displayed in grayscale in a two-dimensional coordinate system in which concentric circles represent elevation angles and vertical and horizontal circles represent azimuth angles. It was confirmed that there were two regions where ΔL* was distributed in concentric circles in the two-dimensional coordinates, and that the two regions were located at approximately symmetrical positions in the two-dimensional coordinates. Regarding the elevation angle at the center of the region where ΔL* is distributed in concentric circles, let one elevation angle be α degrees and the other elevation angle be β degrees. ΔEab at each azimuth angle is calculated based on the difference between the L* value, a* value, and b* value of measurement 1B when the azimuth angle is greater than 0 degrees and less than 359 degrees when the elevation angle is (α+β) / 2, and the L* value, a* value, and b* value of measurement 2B when the azimuth angle is greater than 0 degrees and less than 359 degrees when the elevation angle is (α+β) / 2.

Citation Information

Patent Citations

  • Polarizing plate protection film, polarizing plate and liquid crystal display apparatus using same

    JP2009014886A

  • Polarizing plate protection film, polarizing plate and liquid crystal display apparatus

    JP2010204630A

  • Visibility improving method of liquid crystal display device, and liquid crystal display device using the same

    JP2011107198A